Solid catalyst component for olefin polymerization

The solid catalyst component for olefin polymerization, comprising titanium, magnesium, and an internal electron donor, addresses productivity issues by reducing adhesion and clogging in polymerization devices, enhancing polymer production efficiency.

CN119161509APending Publication Date: 2024-12-20SUMITOMO CHEM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411053803.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-04-27
Filing Date
2021-08-03
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing solid catalyst components for olefin polymerization do not adequately address the issue of improving polymer productivity, particularly in terms of reducing polymer adhesion and clogging in polymerization devices.

Method used

A solid catalyst component for olefin polymerization comprising titanium, magnesium, and an internal electron donor, with specific envelope ratios and production methods that include reacting an organic silicon compound, a titanium compound, and an organic magnesium compound under controlled conditions to produce a catalyst precursor, which is then treated with a halogenated compound and optionally an organic acid halide.

Benefits of technology

The proposed catalyst component enhances polymer productivity by reducing bulk density reduction and adhesion, thereby minimizing device clogging and improving the weight and flow rate of polymer production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a solid catalyst component for olefin polymerization. The present invention produces an olefin-based polymer having little reduction in bulk density due to heating. A solid catalyst component for olefin polymerization, the solid catalyst component for olefin polymerization comprising a titanium atom, a magnesium atom, a halogen atom, and an internal electron donor, and having an envelope degree (E1) within the range of 0.810-0.920, the envelope degree (E1) being calculated by formula (1). E1 = LE1 / LS1 (1) (In formula (1), LE1 represents the envelope circumference of the solid catalyst component for olefin polymerization as determined from an image of the solid catalyst component for olefin polymerization captured by a scanning electron microscope. And LS1 represents the actual circumference of the solid catalyst component for olefin polymerization as determined from an image of the solid catalyst component for olefin polymerization captured by a scanning electron microscope).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application date of August 3, 2021 and application number 202110886041.5. Technical Field

[0002] The present invention relates to a solid catalyst component for olefin polymerization, a catalyst for olefin polymerization, an olefin polymer, a method for producing a solid catalyst component for olefin polymerization, a method for producing a solid catalyst component precursor for olefin polymerization, and a method for producing an olefin polymer. Background Art

[0003] Conventionally, various solid catalyst components containing a titanium atom, a magnesium atom, a halogen atom and an internal electron donor have been proposed as catalyst components for olefin polymerization.

[0004] For example, Patent Document 1 describes a solid catalyst component for producing a propylene block copolymer obtained by contacting a solid catalyst component precursor having a specific large average particle size, a halogenated compound, and an electron donor, thereby enabling the production of a propylene block copolymer having excellent powder properties. On the other hand, when polymerizing olefins, it is desired to improve the productivity of the polymer.

[0005] Prior art literature

[0006] Patent Literature

[0007] [Patent Document 1] Japanese Patent Application Publication No. 2004-182981 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The present invention aims to further improve the productivity of polymers and provides a solid catalyst component for olefin polymerization having specific characteristics, a method for producing the same, an olefin polymer, and the like.

[0010] Means used to solve problems

[0011] The present invention provides the following solutions. [1]

[0013] A solid catalyst component for olefin polymerization, wherein the solid catalyst component for olefin polymerization comprises a titanium atom, a magnesium atom, a halogen atom and an internal electron donor, and

[0014] The envelope E1 calculated by the following formula (1) is in the range of 0.810 to 0.920.

[0015] E1=LE1 / LS1 (1)

[0016] In formula (1),

[0017] LE1 represents the envelope perimeter of the solid catalyst component for olefin polymerization obtained from an image of the solid catalyst component for olefin polymerization taken with a scanning electron microscope,

[0018] LS1 represents the actual circumference of the solid catalyst component for olefin polymerization obtained from an image of the solid catalyst component for olefin polymerization photographed by a scanning electron microscope. [2]

[0020] The solid catalyst component for olefin polymerization according to [1], wherein the E1 is 0.840 to 0.920. [3]

[0022] The solid catalyst component for olefin polymerization according to [2], wherein the E1 is 0.860 to 0.915. [4]

[0024] The solid catalyst component for olefin polymerization as described in any one of [1] to [3], wherein the internal electron donor is at least one compound selected from the group consisting of monoester compounds, aliphatic dicarboxylic acid ester compounds, aromatic dicarboxylic acid ester compounds, diol diester compounds and ether compounds. [5]

[0026] The solid catalyst component for olefin polymerization according to any one of [1] to [4], wherein the internal electron donor is at least one compound selected from the group consisting of aliphatic dicarboxylic acid ester compounds and aromatic dicarboxylic acid ester compounds. [6]

[0028] The solid catalyst component for olefin polymerization according to any one of [1] to [5], wherein the olefin includes at least one component selected from propylene, ethylene and 1-butene. [7]

[0030] An olefin polymerization catalyst comprising an organic aluminum compound and the solid catalyst component for olefin polymerization according to any one of [1] to [6]. [8]

[0032] A method for producing an olefin polymer, comprising the step of polymerizing olefin in the presence of the olefin polymerization catalyst according to [7]. [9]

[0034] A method for producing a solid catalyst component for olefin polymerization, which is a method for producing a solid catalyst component for olefin polymerization containing titanium atoms, magnesium atoms, halogen atoms and an internal electron donor, wherein:

[0035] The method for producing a solid catalyst component for olefin polymerization comprises the steps of obtaining a solid catalyst component precursor for olefin polymerization by reacting an organic silicon compound (a1) having a Si-O bond, a titanium compound (a2) represented by the following formula [I], and an organic magnesium compound (a3), and

[0036] In the above process, Q calculated by the following formula (2) is 0.15 to 0.45,

[0037]

[0038] In formula [I],

[0039] a represents an integer from 1 to 20,

[0040] R 2 represents a hydrocarbon group having 1 to 20 carbon atoms,

[0041] X 2 represents a halogen atom or a hydrocarbonoxy group having 1 to 20 carbon atoms, and the presence of multiple X 2 It can be the same or different;

[0042] Q=D×W×n×VF 0.2 (2)

[0043] In formula (2),

[0044] D represents the ratio of the diameter of the reaction tank to the diameter of the stirring blade.

[0045] W represents the ratio of the blade width of the stirring blade to the blade diameter,

[0046] n is the speed of the stirring blade (rps),

[0047] VF represents the feeding rate (mol / sec) of the organomagnesium compound (a3).

[10]

[0049] The method for producing a solid catalyst component for olefin polymerization according to [9], wherein Q is 0.21 to 0.45.

[11]

[0051] The method for producing a solid catalyst component for olefin polymerization according to

[10] , wherein Q is 0.25 to 0.40.

[12]

[0053] A method for producing a solid catalyst component precursor for olefin polymerization, which is a method for producing a solid catalyst component precursor for olefin polymerization containing titanium atoms, magnesium atoms and halogen atoms, wherein:

[0054] The method for producing a solid catalyst component precursor for olefin polymerization comprises the steps of reacting an organic silicon compound (a1) having a Si-O bond, a titanium compound (a2) represented by the following formula [I], and an organic magnesium compound (a3), and

[0055] In the above process, Q calculated by the following formula (2) is 0.15 to 0.45,

[0056]

[0057] In formula [I],

[0058] a represents an integer from 1 to 20,

[0059] R 2 represents a hydrocarbon group having 1 to 20 carbon atoms,

[0060] X 2 represents a halogen atom or a hydrocarbonoxy group having 1 to 20 carbon atoms, and the presence of multiple X 2 It can be the same or different;

[0061] Q=D×W×n×VF 0.2 (2)

[0062] In formula (2),

[0063] D represents the ratio of the diameter of the reaction tank to the diameter of the stirring blade.

[0064] W represents the ratio of the blade width of the stirring blade to the blade diameter,

[0065] n is the speed of the stirring blade (rps),

[0066] VF represents the feeding rate (mol / sec) of the organomagnesium compound (a3).

[13]

[0068] The method for producing a solid catalyst component precursor for olefin polymerization according to

[12] , wherein Q is 0.21 to 0.45.

[14]

[0070] The method for producing a solid catalyst component precursor for olefin polymerization according to

[13] , wherein Q is 0.25 to 0.40.

[15]

[0072] An olefin polymer, wherein the envelope E2 of the olefin polymer calculated by the following formula (3) is in the range of 0.820 to 0.885,

[0073] E2=LE2 / LS2 (3)

[0074] In formula (3),

[0075] LE2 represents the envelope length of the olefin polymer obtained from an image of the olefin polymer taken with a scanning electron microscope,

[0076] LS2 represents the actual circumference of the olefin polymer obtained from an image of the olefin polymer taken with a scanning electron microscope.

[16]

[0078] The olefin polymer according to

[15] , wherein the bulk density reduction (ΔBD) of the olefin polymer due to heating calculated by the following formula (4) is in the range of -0.012 to -0.000,

[0079] ΔBD=(bulk density at 60°C)-(bulk density at room temperature) (4).

[0080] Effects of the Invention

[0081] According to the present invention, the bulk density reduction (ΔBD (g / cm2) of the olefin polymer produced by heating is 3 )) is small. This means that the mutual adhesion between particles of the manufactured olefin polymer caused by the surface stickiness generated by heating is small. Therefore, if the olefin polymer is manufactured using the solid catalyst component for olefin polymerization of the present invention, the clogging of the polymerization device and the adhesion of the polymer on the wall of the polymerization device are improved. In addition, the productivity of the polymer is improved due to the reasons such as the weight of the olefin polymer that can be manufactured by the polymerization device becoming larger and the flow rate of the gas circulating in the polymerization device becoming larger. BRIEF DESCRIPTION OF THE DRAWINGS

[0082] [ Figure 1 ] Figure 1 This is a plan view of the solid catalyst component 1 for olefin polymerization obtained in Example 1, obtained using a scanning electron microscope.

[0083] [ Figure 2 ] Figure 2 This is a plan view image of the olefin polymer 1 obtained in Example 1, obtained using a scanning electron microscope.

[0084] [ Figure 3 ] Figure 3 This is a plan view image of the solid catalyst component C3 for olefin polymerization obtained in Comparative Example 3, obtained using a scanning electron microscope.

[0085] [ Figure 4 ] Figure 4 This is a plan view image of the olefin polymer C3 obtained in Comparative Example 3, obtained using a scanning electron microscope.

[0086] [ Figure 5 ] Figure 5 This is a diagram for explaining the envelope circumference and actual circumference of a solid catalyst component for olefin polymerization (or an olefin polymer).

[0087] [ Figure 6 ] Figure 6 This is a diagram for explaining how to calculate the perimeter of an envelope. DETAILED DESCRIPTION

[0088] <Solid catalyst component for olefin polymerization (A)>

[0089] The solid catalyst component (A) for olefin polymerization of the present invention is a solid catalyst component for olefin polymerization, comprising a titanium atom, a magnesium atom, a halogen atom and an internal electron donor, and

[0090] The envelope degree E1 calculated by the following formula (1) is in the range of 0.810 to 0.920.

[0091] E1=LE1 / LS1 (1)

[0092] (In formula (1),

[0093] LE1 represents the envelope perimeter of the solid catalyst component for olefin polymerization obtained from an image of the solid catalyst component for olefin polymerization photographed by a scanning electron microscope.

[0094] LS1 represents the actual circumference of the solid catalyst component for olefin polymerization obtained from an image of the solid catalyst component for olefin polymerization taken using a scanning electron microscope.)

[0095] The above E1 is preferably 0.840 to 0.920, and more preferably 0.860 to 0.915.

[0096] In the present specification, the "solid catalyst component for olefin polymerization" refers to a component which exists as a solid in at least toluene and becomes an olefin polymerization catalyst by combining with an olefin polymerization co-catalyst such as an organoaluminum compound.

[0097] A part or all of the titanium atoms in the solid catalyst component for olefin polymerization are derived from the titanium halide compound. A part or all of the halogen atoms in the solid catalyst component for olefin polymerization are derived from the titanium halide compound.

[0098] A part or all of the magnesium atoms in the solid catalyst component for olefin polymerization may be derived from metallic magnesium or a magnesium compound. In addition, a part of the halogen atoms in the solid catalyst component for olefin polymerization may be derived from a magnesium compound.

[0099] The specific surface area of ​​the solid catalyst component for olefin polymerization is usually 100 m 2 / g~700m 2 / g, preferably 200m 2 / g~600m 2 / g, more preferably 300m 2 / g~500m 2 The specific surface area of ​​the solid catalyst component for olefin polymerization can be measured using a gas adsorption measuring device.

[0100] <Method for producing solid catalyst component (A) for olefin polymerization>

[0101] <Method for producing solid catalyst component precursor (a) for olefin polymerization>

[0102] The method for producing a solid catalyst component (A) for olefin polymerization of the present invention is a method for producing a solid catalyst component for olefin polymerization containing a titanium atom, a magnesium atom, a halogen atom and an internal electron donor, wherein:

[0103] The method for producing a solid catalyst component for olefin polymerization comprises the steps of obtaining a solid catalyst component precursor for olefin polymerization by reacting an organic silicon compound (a1) having a Si-O bond, a titanium compound (a2) represented by the following formula [I], and an organic magnesium compound (a3), and

[0104] In the above step, Q calculated by the following formula (2) is 0.15 to 0.45.

[0105]

[0106] (In formula [I],

[0107] a represents an integer of 1 to 20.

[0108] R 2 It represents a hydrocarbon group having 1 to 20 carbon atoms.

[0109] X 2 represents a halogen atom or a hydrocarbonoxy group having 1 to 20 carbon atoms, and the presence of multiple X 2 Can be the same or different.)

[0110] Q=D×W×n×VF 0.2 (2)

[0111] (In formula (2),

[0112] D represents the ratio of the tank diameter of the reaction tank to the blade diameter of the stirring blade.

[0113] W represents the ratio of the blade width of the stirring blade to the blade diameter.

[0114] n represents the rotation speed of the stirring blade (rps).

[0115] VF represents the feeding rate of the organomagnesium compound (a3) ​​(mol / s).

[0116] The Q is preferably 0.21 to 0.45, and more preferably 0.25 to 0.40.

[0117] The method for producing a solid catalyst component precursor (a) for olefin polymerization of the present invention is a method for producing a solid catalyst component precursor for olefin polymerization containing a titanium atom, a magnesium atom and a halogen atom, wherein:

[0118] The method for producing a solid catalyst component precursor for olefin polymerization comprises the steps of reacting an organic silicon compound (a1) having a Si-O bond, a titanium compound (a2) represented by the following formula [I], and an organic magnesium compound (a3), and

[0119] In the above step, Q calculated by the following formula (2) is 0.15 to 0.45.

[0120]

[0121] (In formula [I],

[0122] a represents an integer of 1 to 20.

[0123] R 2 It represents a hydrocarbon group having 1 to 20 carbon atoms.

[0124] X 2 represents a halogen atom or a hydrocarbonoxy group having 1 to 20 carbon atoms, and the presence of multiple X 2 Can be the same or different.)

[0125] Q=D×W×n×VF 0.2 (2)

[0126] (In formula (2),

[0127] D represents the ratio of the tank diameter of the reaction tank to the blade diameter of the stirring blade.

[0128] W represents the ratio of the blade width of the stirring blade to the blade diameter.

[0129] n represents the rotation speed of the stirring blade (rps).

[0130] VF represents the feeding rate of the organomagnesium compound (a3) ​​(mol / s).

[0131] The Q is preferably 0.21 to 0.45, and more preferably 0.25 to 0.40.

[0132] The solid catalyst component (A) for olefin polymerization of the present invention is preferably obtained by contacting the following (a), (b) and (c). In addition, if an organic acid halide (d) is also used as a contact component, the stereoregular polymerization ability is more excellent, which is preferred. That is, the solid catalyst component (A) for olefin polymerization of the present invention is preferably obtained by contacting the following (a), (b), (c) and (d).

[0133] (a) A solid catalyst component precursor obtained by reducing a titanium compound (a2) represented by the following general formula [I] with an organomagnesium compound (a3) ​​in the presence of an organosilicon compound (a1) having a Si—O bond:

[0134]

[0135] (In formula [I], a represents a number from 1 to 20, R 2 represents a hydrocarbon group having 1 to 20 carbon atoms. 2 represents a halogen atom or a hydrocarbonoxy group having 1 to 20 carbon atoms, all X 2 Can be the same or different.)

[0136] (b) Halogenated compounds

[0137] (c) Internal electron donor

[0138] (d) Organic acid halides.

[0139] In addition, when the ester compound (a4) is present as an optional component during the reduction reaction, the polymerization activity and stereoregular polymerization ability are further improved, which is preferred.

[0140] (a) Solid catalyst component precursor

[0141] The solid catalyst component precursor (a) is preferably obtained by reducing a titanium compound (a2) represented by the following general formula [I] with an organomagnesium compound (a3) ​​in the presence of an organosilicon compound (a1) having a Si—O bond.

[0142]

[0143] (In formula [I], a represents a number from 1 to 20, R 2 represents a hydrocarbon group having 1 to 20 carbon atoms. 2 represents a halogen atom or a hydrocarbonoxy group having 1 to 20 carbon atoms, all X 2 Can be the same or different.)

[0144] At this time, when the ester compound (a4) is allowed to coexist as an optional component, the polymerization activity and stereoregular polymerization ability are further improved, which is preferred.

[0145] Examples of the organosilicon compound (a1) having a Si—O bond include organosilicon compounds represented by the following general formula.

[0146] Si(OR 10 ) t R 11 4-t

[0147] R 12 (R 13 2SiO) u S i 14 3 or

[0148] (R 15 2SiO) v

[0149] Here, R 10 represents a hydrocarbon group having 1 to 20 carbon atoms, R 11 , R 12 , R 13 , R 14 and R 15 Each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a hydrogen atom. t represents an integer satisfying 0<t≤4, u represents an integer of 1 to 1000, and v represents an integer of 2 to 1000.

[0150] Specific examples of such organic silicon compounds include tetramethoxysilane, dimethyldimethoxysilane, tetraethoxysilane, triethoxyethylsilane, diethoxydiethylsilane, ethoxytriethylsilane, tetraisopropoxysilane, diisopropoxydiisopropylsilane, tetrapropoxysilane, dipropoxydipropylsilane, tetrabutoxysilane, dibutoxydibutylsilane, dicyclopentyloxydiethylsilane, diethoxydiphenylsilane, cyclohexyloxytrimethylsilane, phenoxytrimethylsilane, tetraphenoxysilane, triethoxyphenylsilane, hexamethyldisiloxane, hexaethyldisiloxane, hexapropyldisiloxane, octaethyltrisiloxane, dimethylpolysiloxane, diphenylpolysiloxane, methylhydrogenpolysiloxane, phenylhydrogenpolysiloxane, and the like.

[0151] Among these organosilicon compounds, the preferred organosilicon compounds are those having the general formula Si(OR 10 ) t R 11 4-t In this case, t is preferably a number satisfying 1≤t≤4, and is particularly preferably tetraalkoxysilane with t=4, and most preferably tetraethoxysilane.

[0152] The titanium compound (a2) is a titanium compound represented by the following general formula [I].

[0153]

[0154] (In formula [I], a represents a number from 1 to 20, R 2 represents a hydrocarbon group having 1 to 20 carbon atoms. 2 represents a halogen atom or a hydrocarbonoxy group having 1 to 20 carbon atoms, all X 2 Can be the same or different.)

[0155] As R 2 Specific examples include: alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, isopentyl, hexyl, heptyl, octyl, decyl, and dodecyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; cycloalkyl groups such as cyclohexyl and cyclopentyl; alkenyl groups such as propenyl; aralkyl groups such as benzyl, and the like.

[0156] Among these groups, an alkyl group having 2 to 18 carbon atoms or an aryl group having 6 to 18 carbon atoms is preferred. A linear alkyl group having 2 to 18 carbon atoms is particularly preferred.

[0157] As X 2 The halogen atom in X may be exemplified by a chlorine atom, a bromine atom, and an iodine atom. A chlorine atom is particularly preferred. 2 The hydrocarbonoxy group having 1 to 20 carbon atoms is 2 Similarly, a hydrocarbonoxy group of a hydrocarbon group having 1 to 20 carbon atoms. 2 In particular, an alkoxy group having a linear alkyl group having 2 to 18 carbon atoms is preferred.

[0158] In the titanium compound represented by the general formula [I], a represents a number of 1 to 20, and is preferably a number satisfying 1≤a≤5.

[0159] Specific examples of such titanium compounds include tetramethoxytitanium, tetraethoxytitanium, tetra-n-propoxytitanium, tetraisopropoxytitanium, tetra-n-butoxytitanium, tetraisobutoxytitanium, n-butoxytitanium trichloride, di-n-butoxytitanium dichloride, tri-n-butoxytitanium chloride, polytetraisopropyl titanate (a=mixture in the range of 2 to 10), polytetra-n-butyl titanate (a=mixture in the range of 2 to 10), polytetra-n-hexyl titanate (a=mixture in the range of 2 to 10), and polytetra-n-octyl titanate (a=mixture in the range of 2 to 10). In addition, condensates of tetraalkoxytitanium obtained by reacting a small amount of water with tetraalkoxytitanium can also be mentioned.

[0160] The titanium compound (a2) is preferably a titanium compound represented by the above general formula [I] wherein a is 1, 2 or 4.

[0161] Tetra-n-butoxytitanium, tetra-n-butoxytitanium dimer or tetra-n-butoxytitanium tetramer is particularly preferred.

[0162] In addition, the titanium compound (a2) may be used in a state of mixing two or more kinds thereof.

[0163] The organomagnesium compound (a3) ​​is any type of organomagnesium compound having a magnesium-carbon bond. In particular, the organomagnesium compound represented by the general formula R 16 MgX 5 (where Mg represents a magnesium atom, R 16 represents a hydrocarbon group having 1 to 20 carbon atoms, X 5 represents a halogen atom) or a Grignard compound represented by the general formula R 17 R 18 Mg (where Mg represents a magnesium atom, R 17 and R 18 Each represents a hydrocarbon group having 1 to 20 carbon atoms). 17 With R 18 They can be the same or different. 16 ~R 18 Specific examples include alkyl groups, aryl groups, aralkyl groups and alkenyl groups having 1 to 20 carbon atoms, such as methyl group, ethyl group, propyl group, isopropyl group, butyl group, sec-butyl group, tert-butyl group, isopentyl group, hexyl group, octyl group, 2-ethylhexyl group, phenyl group and benzyl group.

[0164] In particular, from the perspective of catalyst performance, it is preferred to use R 16 MgX 5 Represents a Grignard compound.

[0165] A hydrocarbon-soluble complex of the above-mentioned organomagnesium compound and an organometallic compound capable of dissolving the organomagnesium compound in hydrocarbons may also be used. Examples of the organometallic compound include compounds of Li, Be, B, Al or Zn.

[0166] As the ester compound (a4), monocarboxylic acid ester or polycarboxylic acid ester can be used, and examples thereof include saturated aliphatic carboxylic acid ester, unsaturated aliphatic carboxylic acid ester, alicyclic carboxylic acid ester, and aromatic carboxylic acid ester. As specific examples, methyl acetate, ethyl acetate, phenyl acetate, methyl propionate, ethyl propionate, ethyl butyrate, ethyl valerate, ethyl acrylate, methyl methacrylate, ethyl benzoate, butyl benzoate, methyl methylbenzoate, ethyl methylbenzoate, ethyl anisate, diethyl succinate, dibutyl succinate, diethyl malonate, dibutyl malonate, dimethyl maleate, dibutyl maleate, diethyl itaconate, dibutyl itaconate, phthalic acid, Monoethyl phthalate, dimethyl phthalate, methyl ethyl phthalate, diethyl phthalate, di-n-propyl phthalate, diisopropyl phthalate, di-n-butyl phthalate, diisobutyl phthalate, dipentyl phthalate, di-n-hexyl phthalate, diheptyl phthalate, di-n-octyl phthalate, di(2-ethylhexyl) phthalate, diisodecyl phthalate, dicyclohexyl phthalate, diphenyl phthalate, etc.

[0167] Among these ester compounds, unsaturated aliphatic carboxylic acid esters such as methacrylate and maleate, and aromatic carboxylic acid esters such as phthalate are preferred, and dialkyl esters of phthalic acid are particularly preferably used.

[0168] The solid catalyst component precursor (a) is preferably obtained by reducing the titanium compound (a2) with an organomagnesium compound (a3) ​​in the presence of an organosilicon compound (a1) or in the presence of an organosilicon compound (a1) and an ester compound (a4).

[0169] The titanium compound (a2), the organosilicon compound (a1) and the ester compound (a4) are preferably used after being dissolved or diluted in an appropriate solvent.

[0170] Examples of such solvents include aliphatic hydrocarbons such as hexane, heptane, octane, and decane; aromatic hydrocarbons such as toluene and xylene; alicyclic hydrocarbons such as cyclohexane, methylcyclohexane, and decalin; and ether compounds such as diethyl ether, dibutyl ether, diisoamyl ether, and tetrahydrofuran.

[0171] The reduction reaction temperature is usually in the range of -50°C to 70°C, preferably in the range of -30°C to 50°C, and particularly preferably in the range of -25°C to 35°C.

[0172] The reaction time is not particularly limited, but is usually about 30 minutes to about 10 hours.

[0173] In addition, during the reduction reaction, porous supports such as inorganic oxides and organic polymers can be coexisted, and the solid product can be impregnated into the porous support. As the porous support used, it can be a known porous support. It can be listed as: porous inorganic oxides represented by SiO2, Al2O3, MgO, TiO2, ZrO2, etc.; or organic porous polymers such as polystyrene, styrene-divinylbenzene copolymer, styrene-ethylene glycol-methyl dimethacrylate copolymer, polymethyl acrylate, polyethyl acrylate, methyl acrylate-divinylbenzene copolymer, polymethyl methacrylate, methyl methacrylate-divinylbenzene copolymer, polyacrylonitrile, acrylonitrile-divinylbenzene copolymer, polyvinyl chloride, polyethylene, polypropylene, etc. Among these substances, it is preferred to use an organic porous polymer, among which styrene-divinylbenzene copolymer or acrylonitrile-divinylbenzene copolymer is particularly preferred.

[0174] The pore radius of the porous carrier is The pore volume in the range is preferably 0.3 cc / g or more, more preferably 0.4 cc / g or more, and the pore volume in this range is preferably The pore volume of the porous carrier is 35% or more, more preferably 40% or more. When the pore volume of the porous carrier is small, the catalyst component may not be effectively fixed, which is not preferred. In addition, even if the pore volume of the porous carrier is 0.3 cc / g or more, if it is not sufficiently present in the porous carrier, the catalyst component may not be effectively fixed. If the pore radius is within the range of 0.1 Å, the catalyst component may not be effectively fixed, which is not preferred.

[0175] Such a solid catalyst component precursor used in the present invention can be adjusted by performing the above-mentioned reduction reaction under stirring conditions.

[0176] During such stirring, the reaction temperature is usually -5°C to 50°C, preferably 0°C to 25°C, and more preferably 5°C to 10°C.

[0177] During such stirring, the amount of the solvent is usually (a1+a2) / (a1+a2+solvent)=20 ml / ml to 60 ml / ml, more preferably 30 ml / ml to 50 ml / ml.

[0178] In such stirring, regarding the reaction component ratio, the ratio of a1 to a3 is generally Si / Mg=0.4 mol / mol to 5 mol / mol, preferably 0.6 mol / mol to 2 mol / mol, and more preferably 0.8 mol / mol to 1 mol / mol, based on the atomic ratio of the Si atoms and Mg atoms contained. In addition, the ratio of a2 to a3 is generally Ti / Mg=0.01 mol / mol to 0.15 mol / mol, preferably 0.03 mol / mol to 0.1 mol / mol, and more preferably 0.05 mol / mol to 0.07 mol / mol, based on the atomic ratio of the Ti atoms and Mg atoms contained. In the case of also using a4 as an optional component, the ratio of a4 to a3 is generally ester group / Mg=0.003 mol / mol to 0.08 mol / mol, and preferably 0.006 mol / mol to 0.06 mol / mol, based on the ratio of the ester group contained to the Mg atom.

[0179] The solid catalyst component precursor obtained by the reduction reaction is usually subjected to solid-liquid separation and washed several times with an inert hydrocarbon solvent such as hexane, heptane, toluene, or the like.

[0180] In addition, from the viewpoint of polymerization activity and stereoregularity, the solid catalyst component precursor used in the present invention is preferably heat-treated in advance when preparing the solid catalyst component. The heat treatment is preferably carried out in a slurry state in an inert hydrocarbon solvent. The treatment temperature is usually 40°C to 120°C, preferably 60°C to 100°C. The treatment time is usually in the range of 30 minutes to 10 hours.

[0181] The solid catalyst component precursor obtained in this manner contains trivalent titanium atoms, magnesium atoms and hydrocarbyloxy groups, and generally exhibits amorphous properties or extremely weak crystallinity. From the viewpoint of catalyst performance, an amorphous structure is particularly preferred.

[0182] (b) Halogenated compounds

[0183] The halogenated compound is preferably a compound capable of replacing the hydrocarbyloxy group in the solid catalyst component precursor (a) with a halogen atom, and among them, a halogen compound of a Group 4 element, a halogen compound of a Group 13 element, or a halogen compound of a Group 14 element is preferred.

[0184] As the halogen compound of the Group 4 element, preferably, 9 ) b X 4 4-b (wherein, M represents a Group 4 element, R 9 represents a hydrocarbon group having 1 to 20 carbon atoms, X 4represents a halogen atom, and b represents a number satisfying 0≤b<4). Specific examples of M include titanium, zirconium, and hafnium, among which titanium is preferred. 9 Specific examples include: alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, isopentyl, tert-pentyl, hexyl, heptyl, octyl, decyl, and dodecyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; alkenyl groups such as propenyl; aralkyl groups such as benzyl, etc. Among them, alkyl groups having 2 to 18 carbon atoms or aryl groups having 6 to 18 carbon atoms are preferred. Straight-chain alkyl groups having 2 to 18 carbon atoms are particularly preferred. In addition, groups having two or more different OR 9 Halogen compounds of Group 4 elements.

[0185] As X 4 Examples of the halogen atom represented by include a chlorine atom, a bromine atom, and an iodine atom. Among them, a chlorine atom can give particularly preferred results.

[0186] By the general formula M(OR 9 ) b X 4 4-b In the halogen compound of the Group 4 element represented by , b is a number satisfying 0≤b<4, preferably a number satisfying 0≤b≤2, and particularly preferably b=0.

[0187] Specifically, as represented by the general formula M(OR 9 ) b X 4 4-b Halogen compounds of Group 4 elements represented by , include: titanium tetrahalides such as titanium tetrachloride, titanium tetrabromide, and titanium tetraiodide; alkoxy titanium trihalides such as methoxy titanium trichloride, ethoxy titanium trichloride, butoxy titanium trichloride, phenoxy titanium trichloride, and ethoxy titanium tribromide; dialkoxy titanium dihalides such as dimethoxy titanium dichloride, diethoxy titanium dichloride, dibutoxy titanium dichloride, diphenoxy titanium dichloride, and diethoxy titanium dibromide; and zirconium compounds and hafnium compounds corresponding to them. Titanium tetrachloride is most preferred.

[0188] As the halogen compound of a Group 13 element or a Group 14 element, preferably, m-a X a (wherein, M represents an atom of Group 13 or Group 14, R represents a hydrocarbon group having 1 to 20 carbon atoms, X represents a halogen atom, and m represents the valence of M. a represents a number satisfying 0<a≤m).

[0189] As the Group 13 atom mentioned here, B, Al, Ga, In, and Tl can be listed, preferably B or Al, and more preferably Al. In addition, as the Group 14 atom, C, Si, Ge, Sn, and Pb can be listed, preferably Si, Ge, or Sn, and more preferably Si or Sn.

[0190] m is the valence of M. For example, when M is Si, m=4.

[0191] a represents a number satisfying 0<a≤m, and when M is Si, a is preferably 3 or 4.

[0192] Examples of the halogen atom represented by X include F, Cl, Br, and I, and Cl is preferred.

[0193] Specific examples of R include: alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, pentyl, isopentyl, hexyl, heptyl, octyl, decyl, and dodecyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; cycloalkyl groups such as cyclohexyl and cyclopentyl; alkenyl groups such as propenyl; aralkyl groups such as benzyl, etc. Preferably, R is an alkyl group or an aryl group, and particularly preferably, R is methyl, ethyl, n-propyl, phenyl, or p-tolyl.

[0194] Specific examples of halogen compounds of Group 13 elements include boron trichloride, methylboron dichloride, ethylboron dichloride, phenylboron dichloride, cyclohexylboron dichloride, dimethylboron chloride, methylethylboron chloride, aluminum trichloride, methylaluminum dichloride, ethylaluminum dichloride, phenylaluminum dichloride, cyclohexylaluminum dichloride, dimethylaluminum chloride, diethylaluminum chloride, methylethylaluminum chloride, ethylaluminum sesquichloride, gallium chloride, gallium dichloride, gallium trichloride, methylgallium dichloride, ethylgallium dichloride, phenylgallium dichloride, cyclohexylgallium dichloride, dimethylgallium chloride, methylethylgallium chloride, indium chloride, indium trichloride, methylindium dichloride, phenylindium dichloride, dimethylindium chloride, thallium chloride, thallium trichloride, methylthallium dichloride, phenylthallium dichloride, and dimethylthallium chloride. Examples also include compounds in which chlorine in the names of these compounds is replaced with fluorine, bromine, or iodine.

[0195] Specific examples of the halogen compounds of Group 14 elements include tetrachloromethane, chloroform, dichloromethane, monochloromethane, 1,1,1-trichloroethane, 1,1-dichloroethane, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, tetrachlorosilane, trichlorosilane, methyltrichlorosilane, ethyltrichlorosilane, n-propyltrichlorosilane, n-butyltrichlorosilane, phenyltrichlorosilane, benzyltrichlorosilane, p-tolyltrichlorosilane, cyclohexyltrichlorosilane, dichlorosilane, methyldichlorosilane, ethyldichlorosilane, dimethyldichlorosilane, diphenyldichlorosilane, methylethyldichlorosilane, monochlorosilane, trimethylchlorosilane, triphenyltrichlorosilane, and Examples of the present invention include chlorosilane, tetrachlorogermane, trichlorogermane, methyltrichlorogermane, ethyltrichlorogermane, phenyltrichlorogermane, dichlorogermane, dimethyldichlorogermane, diethyldichlorogermane, diphenyldichlorogermane, monochlorogermane, trimethylchlorogermane, triethylchlorogermane, tri-n-butylchlorogermane, tin tetrachloride, methyltin trichloride, n-butyltin trichloride, dimethyltin dichloride, di-n-butyltin dichloride, diisobutyltin dichloride, diphenyltin dichloride, divinyltin dichloride, methyltin trichloride, phenyltin trichloride, lead dichloride, methyllead chloride, and phenyllead chloride. Compounds in which the chlorine in the names of these compounds is replaced by fluorine, bromine, or iodine may also be mentioned.

[0196] As the halogenated compound (b), titanium tetrachloride, methylaluminum dichloride, ethylaluminum dichloride, tetrachlorosilane, phenyltrichlorosilane, methyltrichlorosilane, ethyltrichlorosilane, n-propyltrichlorosilane or tin tetrachloride is particularly preferably used from the viewpoint of polymerization activity.

[0197] As the halogenated compound (b), only one kind of the above-mentioned compounds may be used, or a plurality of kinds may be used.

[0198] (c) Internal electron donor

[0199] The internal electron donor (c) refers to an organic compound that can donate electron pairs to one or more metal atoms contained in the solid catalyst component for olefin polymerization, and specifically includes: monoester compounds (including β-alkoxy ester compounds), dicarboxylic acid ester compounds (aliphatic dicarboxylic acid ester compounds, aromatic dicarboxylic acid ester compounds), diol diester compounds and ether compounds, etc. Preferably, the internal electron donor (c) is at least one compound selected from the group consisting of aliphatic dicarboxylic acid ester compounds and aromatic dicarboxylic acid ester compounds.

[0200] The monoester compound refers to an organic compound having one ester bond (-CO-O-) in the molecule, and is preferably an aromatic carboxylic acid ester compound and an aliphatic carboxylic acid ester compound. Examples of the aromatic carboxylic acid ester compound include methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, pentyl benzoate, hexyl benzoate, octyl benzoate, methyl methyl benzoate, ethyl methyl benzoate, propyl methyl benzoate, butyl methyl benzoate, pentyl methyl benzoate, hexyl methyl benzoate, and octyl methyl benzoate. Examples of the aliphatic carboxylic acid ester compounds include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, pentyl acetate, hexyl acetate, octyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, pentyl propionate, hexyl propionate, octyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, pentyl butyrate, hexyl butyrate, octyl butyrate, methyl valerate, ethyl valerate, propyl valerate, valeric acid Butyl ester, pentyl valerate, hexyl valerate, octyl valerate, methyl hexanoate, ethyl hexanoate, propyl hexanoate, butyl hexanoate, pentyl hexanoate, hexyl hexanoate, octyl hexanoate, methyl heptanoate, ethyl heptanoate, propyl heptanoate, butyl heptanoate, pentyl heptanoate, hexyl heptanoate, octyl heptanoate, methyl octanoate, ethyl octanoate, propyl octanoate, butyl octanoate, pentyl octanoate, hexyl octanoate, octyl octanoate, methyl nonanoate, ethyl nonanoate, propyl nonanoate, nonanoate butyl laurate, ethyl laurate, propyl laurate, butyl laurate, amyl laurate, hexyl laurate, octyl laurate, methyl myristate, ethyl myristate, propyl myristate, butyl myristate, amyl myristate, hexyl myristate, octyl laurate, Octyl myristic acid, methyl palmitate, ethyl palmitate, propyl palmitate, butyl palmitate, pentyl palmitate, hexyl palmitate, octyl palmitate, methyl heptadecanoate, ethyl heptadecanoate, propyl heptadecanoate, butyl heptadecanoate, pentyl heptadecanoate, hexyl heptadecanoate, octyl heptadecanoate, methyl stearate, ethyl stearate, propyl stearate, butyl stearate, pentyl stearate, hexyl stearate and octyl stearate, etc.

[0201] The dicarboxylic acid ester compound is a compound having two ester bonds (—CO—O—) in the molecule and having a structure obtained by esterifying two carboxyl groups of a dicarboxylic acid with a monohydric alcohol, and is preferably an aromatic dicarboxylic acid ester compound or an aliphatic dicarboxylic acid ester compound. The aromatic dicarboxylic acid ester compound is, for example, a compound that can be synthesized from an aromatic dicarboxylic acid or an aromatic dicarboxylic acid dihalide and a monohydric alcohol, and specifically includes: dimethyl phthalate, methyl ethyl phthalate, diethyl phthalate, di-n-propyl phthalate, diisopropyl phthalate, di-n-butyl phthalate, diisobutyl phthalate, dipentyl phthalate, di-n-hexyl phthalate, diheptyl phthalate, di-n-octyl phthalate, di(2-ethylhexyl) phthalate, diisodecyl phthalate, dicyclohexyl phthalate, diphenyl phthalate, and the like.The aliphatic dicarboxylic acid ester compound is, for example, a compound that can be synthesized from an aliphatic dicarboxylic acid or an aliphatic dicarboxylic acid dihalide and a monohydric alcohol, and specifically includes dimethyl oxalate, diethyl oxalate, dipropyl oxalate, dibutyl oxalate, dipentyl oxalate, dihexyl oxalate, dioctyl oxalate, dimethyl malonate, diethyl malonate, dipropyl malonate, dibutyl malonate, dipentyl malonate, dihexyl malonate, dioctyl malonate, dimethyl succinate, diethyl succinate, dipropyl succinate, dibutyl succinate, dipentyl succinate, dihexyl succinate, dioctyl succinate, dimethyl glutarate, diethyl glutarate, dipropyl glutarate, dibutyl glutarate, Dipentyl glutarate, dihexyl glutarate, dioctyl glutarate, dimethyl adipate, diethyl adipate, dipropyl adipate, dibutyl adipate, dipentyl adipate, dihexyl adipate, dioctyl adipate, dimethyl fumarate, diethyl fumarate, dipropyl fumarate, dibutyl fumarate, dipentyl fumarate, dihexyl fumarate, dioctyl fumarate, dimethyl maleate, diethyl maleate, dipropyl maleate, dibutyl maleate, dipentyl maleate, dihexyl maleate, dioctyl maleate, dimethyl cyclohexane-1,2-dicarboxylate, diethyl cyclohexane-1,2-dicarboxylate, dipropyl cyclohexane-1,2-dicarboxylate, dibutyl cyclohexane-1,2-dicarboxylate, cyclohexane -1,2-dipentyl dicarboxylate, cyclohexane-1,2-dicarboxylic acid dihexyl ester, cyclohexane-1,2-dicarboxylic acid dioctyl ester, 1,2-cyclohexene-1,2-dicarboxylic acid dimethyl ester, 1,2-cyclohexene-1,2-dicarboxylic acid diethyl ester, 1,2-cyclohexene-1,2-dicarboxylic acid dipropyl ester, 1,2-cyclohexene-1,2-dicarboxylic acid dibutyl ester, 1,2-cyclohexene-1,2-dicarboxylic acid dipentyl ester, 1,2-cyclohexene-1,2-dicarboxylic acid dihexyl ester, 1,2-cyclohexene-1,2-dicarboxylic acid dioctyl ester, 3-methylcyclohexane-1,2-dicarboxylic acid dimethyl ester, 3-methylcyclohexane-1,2-dicarboxylic acid diethyl ester, 3-methylcyclohexane-1,2-dicarboxylic acid dipropyl ester , 3-methylcyclohexane-1,2-dicarboxylic acid dibutyl ester, 3-methylcyclohexane-1,2-dicarboxylic acid dipentyl ester, 3-methylcyclohexane-1,2-dicarboxylic acid dihexyl ester, 3-methylcyclohexane-1,2-dicarboxylic acid dioctyl ester, 3,6-dimethylcyclohexane-1,2-dicarboxylic acid dimethyl ester, 3,6-dimethylcyclohexane-1,2-dicarboxylic acid diethyl ester, 3,6-dimethylcyclohexane-1,2-dicarboxylic acid dipropyl ester, 3,6-dimethylcyclohexane-1,2-dicarboxylic acid dibutyl ester, 3,6-dimethylcyclohexane-1,2-dicarboxylic acid dipentyl ester, 3,6-dimethylcyclohexane-1,2-dicarboxylic acid dihexyl ester and 3,6-dimethylcyclohexane-1,2-dicarboxylic acid dioctyl ester, etc.

[0202] The diol diester compound refers to a compound having two ester bonds (-CO-O-) in the molecule and having a structure in which the two hydroxyl groups of the diol are each esterified with the carboxyl groups of a monocarboxylic acid or a dicarboxylic acid, and specific examples thereof include 1,2-propylene glycol dibenzoate, 1,2-propylene glycol diacetate, 1,2-butylene glycol dibenzoate, 1,2-butylene glycol diacetate, 1,2-cyclohexanediol dibenzoate, 1,2-cyclohexanediol diacetate, 1 ,3-propylene glycol dibenzoate, 1,3-propylene glycol diacetate, 2,4-pentanediol dibenzoate, 2,4-pentanediol diacetate, 1,2-cyclopentanediol dibenzoate, 1,2-cyclopentanediol diacetate, 4-tert-butyl-6-methylcatechol dibenzoate, 4-tert-butyl-6-methylcatechol diacetate, 4-tert-butyl-6-methylresorcinol dibenzoate and 4-tert-butyl-6-methylresorcinol diacetate, etc.

[0203] The β-alkoxy ester compound refers to a compound having an alkoxycarbonyl group and an alkoxy group at the β position of the alkoxycarbonyl group, and specifically includes 2-methoxymethyl-3,3-dimethylbutyric acid methyl ester, 2-methoxymethyl-3,3-dimethylbutyric acid ethyl ester, 2-methoxymethyl-3,3-dimethylbutyric acid propyl ester, 2-methoxymethyl-3,3-dimethylbutyric acid butyl ester, 2-methoxymethyl-3,3-dimethylbutyric acid pentyl ester, 2-methoxymethyl-3,3-dimethylbutyric acid hexyl ester, 2-methoxymethyl-3,3-dimethylbutyric acid octyl ester, 3-methoxy-2-phenylpropionic acid methyl ester, 3-methoxy-2-phenylpropionic acid ethyl ester, 3-methoxy-2-phenylpropionic acid propyl ester, 3-methoxy-2-phenylpropionic acid butyl ester, 3-methoxy-2-phenylpropionic acid pentyl ester, 3-methoxy-2-phenylpropionic acid hexyl ester, 3-methoxy-2-phenylpropionic acid octyl ester, 2-ethoxymethyl-3,3-dimethylbutyric acid methyl ester, 2-ethoxymethyl-3,3-dimethylbutyric acid ethyl ester, 2-ethoxymethyl-3,3-dimethylbutyric acid propyl ester, 2-ethoxymethyl-3,3-dimethylbutyric acid butyl ester, 2-ethoxymethyl-3,3-dimethylbutyric acid pentyl ester, 2-ethoxymethyl-3,3-dimethylbutyric acid hexyl ester, 2-ethoxymethyl-3,3-dimethylbutyric acid octyl ester, 3-ethoxy-2-phenylpropionic acid methyl ester, 3-ethoxy-2-phenylpropionic acid ethyl ester, 3-ethoxy -2-phenylpropionic acid propyl ester, 3-ethoxy-2-phenylpropionic acid butyl ester, 3-ethoxy-2-phenylpropionic acid pentyl ester, 3-ethoxy-2-phenylpropionic acid hexyl ester, 3-ethoxy-2-phenylpropionic acid octyl ester, 2-propoxymethyl-3,3-dimethylbutyric acid methyl ester, 2-propoxymethyl-3,3-dimethylbutyric acid ethyl ester, 2-propoxymethyl-3,3-dimethylbutyric acid propyl ester, 2-propoxymethyl-3,3-dimethylbutyric acid butyl ester, 2-propoxymethyl-3,3-dimethylbutyric acid pentyl ester, 2-propoxymethyl-3,3-dimethylbutyric acid hexyl ester, 2-propoxymethyl-3,3-dimethylbutyric acid octyl ester, 3-propoxy-2-phenylpropionic acid methyl ester, 3-propoxy-2-phenyl Ethyl propionate, propyl 3-propoxy-2-phenylpropionate, butyl 3-propoxy-2-phenylpropionate, pentyl 3-propoxy-2-phenylpropionate, hexyl 3-propoxy-2-phenylpropionate, octyl 3-propoxy-2-phenylpropionate, methyl 2-methoxybenzoate, ethyl 2-methoxybenzoate, propyl 2-methoxybenzoate, butyl 2-methoxybenzoate, pentyl 2-methoxybenzoate, hexyl 2-methoxybenzoate, octyl 2-methoxybenzoate, methyl 2-ethoxybenzoate, ethyl 2-ethoxybenzoate, propyl 2-ethoxybenzoate, butyl 2-ethoxybenzoate, pentyl 2-ethoxybenzoate, hexyl 2-ethoxybenzoate and octyl 2-ethoxybenzoate, etc.

[0204] Specific examples of the ether compound include 1,2-dimethoxypropane, 1,2-diethoxypropane, 1,2-dipropoxypropane, 1,2-dibutoxypropane, 1,2-di-tert-butoxypropane, 1,2-diphenoxypropane, 1,2-dibenzyloxypropane, 1,2-dimethoxybutane, 1,2-diethoxybutane, 1,2-dipropoxybutane, 1,2-dibutoxybutane, 1,2-di-tert-butoxybutane, 1,2-diphenoxybutane, 1,2-dibenzyloxybutane, butane, 1,2-dimethoxycyclohexane, 1,2-diethoxycyclohexane, 1,2-dipropoxycyclohexane, 1,2-dibutoxycyclohexane, 1,2-di-tert-butoxycyclohexane, 1,2-diphenoxycyclohexane, 1,2-dibenzyloxycyclohexane, 1,3-dimethoxypropane, 1,3-diethoxypropane, 1,3-dipropoxypropane, 1,3-dibutoxypropane, 1,3-di-tert-butoxypropane, 1,3-diphenoxypropane, 1,3-dibenzyloxypropane, 2,4-dimethoxycyclohexane, Methoxypentane, 2,4-diethoxypentane, 2,4-dipropoxypentane, 2,4-dibutoxypentane, 2,4-di-tert-butoxypentane, 2,4-diphenoxypentane, 2,4-dibenzyloxypentane, 1,2-dimethoxycyclopentane, 1,2-diethoxycyclopentane, 1,2-dipropoxycyclopentane, 1,2-dibutoxycyclopentane, 1,2-di-tert-butoxycyclopentane, 1,2-diphenoxycyclopentane, 1,2-dibenzyloxycyclopentane, 9,9-bis(methoxymethyl) Fluorene, 9,9-bis(ethoxymethyl)fluorene, 9,9-bis(propoxymethyl)fluorene, 9,9-bis(butoxymethyl)fluorene, 9,9-bis(tert-butoxymethyl)fluorene, 9,9-bis(phenoxymethyl)fluorene, 9,9-bis(benzyloxymethyl)fluorene, 1,2-dimethoxybenzene, 1,2-diethoxybenzene, 1,2-dipropoxybenzene, 1,2-dibutoxybenzene, 1,2-di-tert-butoxybenzene, 1,2-diphenoxybenzene, 1,2-dibenzyloxybenzene, tetrahydrofuran, dibutyl ether and diethyl ether, etc.

[0205] In addition, internal electron donors described in Japanese Patent Application Laid-Open No. 2011-246699 can also be exemplified.

[0206] Among them, dicarboxylic acid ester compounds, diol diester compounds and β-alkoxy ester compounds are preferred. In one example, the internal electron donor is more preferably a β-alkoxy ester compound, and more preferably ethyl 2-ethoxymethyl-3,3-dimethylbutyrate. The internal electron donor can be used alone or in combination of two or more.

[0207] (d) Organic acid halides

[0208] As the organic acid halide (d) used in the preparation of the solid catalyst component of the present invention, monocarboxylic acid halide or polycarboxylic acid halide is preferably used, and examples thereof include aliphatic carboxylic acid halide, alicyclic carboxylic acid halide, and aromatic carboxylic acid halide. Specific examples thereof include acetyl chloride, propionyl chloride, butyryl chloride, valeryl chloride, acryloyl chloride, methacryloyl chloride, benzoyl chloride, methylbenzoyl chloride, anisyl chloride, succinyl chloride, malonyl chloride, maleoyl chloride, itaconyl chloride, and phthaloyl chloride.

[0209] Among these organic acid halides, aromatic carboxylic acid chlorides such as benzoyl chloride, methylbenzoyl chloride and phthaloyl chloride are preferred, aromatic dicarboxylic acid dichlorides are more preferred, and phthaloyl chloride is particularly preferred.

[0210] (A) Preparation of solid catalyst component

[0211] The solid catalyst component (A) of the present invention is preferably obtained by contacting the solid catalyst component precursor (a), the halogenated compound (b) and the internal electron donor (c), or by contacting the solid catalyst component precursor (a), the halogenated compound (b), the internal electron donor (c) and the organic acid halide (d). These contact treatments are usually all carried out under an inert gas atmosphere such as nitrogen or argon.

[0212] Specific methods of the contact treatment for obtaining the solid catalyst component include:

[0213] A method of adding (b) and (c) (in any order) into (a) and performing contact treatment;

[0214] A method in which (b) and (d) (in any order) are added to (a) and the mixture is contacted with each other;

[0215] A method in which a mixture of (b), (c) and (d) is added to (a) and the mixture is contacted with the mixture;

[0216] A method in which a mixture of (b) and (c) and (d) (the order of addition is arbitrary) are added to (a) and the mixture is contacted with each other;

[0217] A method in which (c) is introduced into (a) and subjected to a contact treatment, and then (b) is introduced and subjected to a contact treatment;

[0218] A method in which (c) is added to (a) and subjected to a contact treatment, and then (b) and (c) (in any order of addition) are added and subjected to a contact treatment;

[0219] A method in which (a) is added with (c) and the mixture is then added with (b) and (c) and the mixture is then brought into contact with the mixture;

[0220] A method of adding (a) and (c) (in any order) into (b) and performing contact treatment;

[0221] A method in which (a) and (d) (in any order) are added to (b) and the mixture is contacted with each other;

[0222] · A method of adding (a), (c), and (d) (in any order) to (b) for contact treatment, etc.

[0223] In addition, there may be mentioned a method in which, after these contact treatments, contact treatment with (b) is further performed one or more times, and a method in which contact treatment with a mixture of (b) and (c) is performed one or more times.

[0224] Among them, preferred are methods of adding (b) and (d) (addition order is arbitrary) to (a) and contacting them; methods of adding a mixture of (b) and (c) and (d) (addition order is arbitrary) to (a); methods of adding a mixture of (b) and (c) and (d) (addition order is arbitrary) to (a) and contacting them, and then adding a mixture of (b) and (c) and contacting them once or more; methods of adding (c) to (a) and contacting them, and then contacting them once or more with the mixture of (b) and (c). More preferred are methods of adding a mixture of (b) and (c) and (d) to (a) in that order and contacting them; methods of adding a mixture of (b) and (c) and (d) to (a) in that order and contacting them, and then adding a mixture of (b) and (c) and contacting them once or more; or methods of adding (c) to (a) and contacting them, and then contacting them once or more with the mixture of (b) and (c). Particularly preferred is a method in which a mixture of (b) and (c2) and (d) are added to (a) in that order and contacted with each other, then a mixture of (b), (c1) and (c2) is added and contacted with each other, and further contacted with the mixture of (b) and (c2) is carried out one or more times; or a method in which (c1) is added to (a) and contacted with each other, then a mixture of (b), (c1) and (c2) is added and contacted with each other, and further contacted with the mixture of (b) and (c2) is carried out one or more times.

[0225] From the viewpoint of suppressing the generation of fine powder, the contact treatment is preferably performed in the presence of a diluent.

[0226] After the contact treatment, the next operation may be directly performed, but in order to remove the residual material, it is preferable to perform a washing treatment with a diluent.

[0227] The diluent is preferably inactive against the treatment target component, and can include aliphatic hydrocarbons such as pentane, hexane, heptane, and octane; aromatic hydrocarbons such as benzene, toluene, and xylene; alicyclic hydrocarbons such as cyclohexane and cyclopentane; and halogenated hydrocarbons such as 1,2-dichloroethane and monochlorobenzene.

[0228] For each step of the contact treatment, the amount of the diluent used in the contact treatment is usually 0.1 ml to 1000 ml per 1 g of the solid catalyst component precursor (a). Preferably, the amount of the diluent used in the contact treatment is 1 ml to 100 ml per 1 g of the solid catalyst component precursor (a). In addition, the amount of the diluent used in one washing operation is also the same. For each step of the contact treatment, the number of washing operations in the washing treatment is usually 1 to 5 times.

[0229] The temperature of the contact treatment and / or the washing treatment is usually -50°C to 150°C, preferably 0°C to 140°C, and more preferably 60°C to 135°C.

[0230] The contact treatment time is not particularly limited, but is preferably 0.5 to 8 hours, more preferably 1 to 6 hours. The washing operation time is not particularly limited, but is preferably 1 to 120 minutes, more preferably 2 to 60 minutes.

[0231] The amount of the halogenated compound (b) used is usually 0.5 to 1000 mmol, preferably 1 to 200 mmol, and more preferably 2 to 100 mmol, based on 1 g of the solid catalyst component precursor (a).

[0232] When the halogenated compound (b) is used, it is preferably used together with the internal electron donor (c). In this case, the amount of (c) used is usually 1 mol to 100 mol, preferably 1.5 mol to 75 mol, and more preferably 2 mol to 50 mol, relative to 1 mol of (b).

[0233] The amount of the internal electron donor (c) used is usually 0.01 to 100 mmol, preferably 0.05 to 50 mmol, and more preferably 0.1 to 20 mmol, based on 1 g of the solid catalyst component precursor (a).

[0234] The amount of the organic acid halide (d) used is usually 0.1 mmol to 100 mmol, preferably 0.3 mmol to 50 mmol, and more preferably 0.5 mmol to 20 mmol, relative to 1 g of the solid catalyst component precursor (a). In addition, the amount of the organic acid halide (d) used is usually 0.01 mol to 1.0 mol, preferably 0.03 mol to 0.5 mol, relative to 1 mol of magnesium atoms in the solid catalyst component precursor (a).

[0235] When the amount of (c) or (d) used is too large, the particles may collapse.

[0236] In addition, when each compound is used for the contact treatment multiple times, the usage amount of each compound described above means the usage amount of each compound per time.

[0237] The obtained solid catalyst component can be used for polymerization in a slurry state in combination with an inactive diluent, or in the form of a fluid powder obtained by drying. As the drying method, there can be cited: a method of removing volatile components under reduced pressure, a method of removing volatile components under the circulation of an inert gas such as nitrogen and argon. The temperature during drying is preferably 0°C to 200°C, more preferably 50°C to 100°C. The drying time is preferably 0.01 hour to 20 hours, more preferably 0.5 hour to 10 hours.

[0238] In the step of obtaining the solid catalyst component precursor (a) and the step of obtaining the solid catalyst component for olefin polymerization (A), there is no particular restriction on the rotation speed n (rps) of the stirring blade, and for example, it is in the range of 0.2 rps to 170 rps. In addition, there is no particular restriction on the blade diameter (m) of the stirring blade, and for example, each is independently in the range of 0.01 m to 1 m. There is no particular restriction on the shape of the stirring blade, and for example, it is a paddle blade, a propeller blade, a turbine blade, or an anchor blade.

[0239] The shape of the reaction tank used in the step of obtaining the solid catalyst component precursor (a) and the step of obtaining the solid catalyst component for olefin polymerization (A) is not particularly limited, and may be, for example, a cylindrical shape with a circular bottom (also referred to as a disk shape) or an elliptical cylindrical shape with an elliptical bottom. The reaction tank may have a baffle, and the shape of the baffle is not particularly limited, and may be, for example, a shape having 1 to 6 flat plates. The ratio D of the tank diameter of the reaction tank to the blade diameter of the stirring blade is not particularly limited, and may be, for example, 1.05 to 3.00, preferably 1.10 to 2.00. The ratio W of the blade width of the stirring blade to the blade diameter is not particularly limited, and may be, for example, 0.03 to 2.50, preferably 0.08 to 1.20, and more preferably 0.09 to 0.50. The rate VF of introduction of the organomagnesium compound (a3) ​​is not particularly limited, and may be, for example, 0.000001 mol / sec to 10 mol / sec, and preferably 0.00001 mol / sec to 1 mol / sec.

[0240] In one example, the content of titanium atoms in the solid catalyst component for olefin polymerization is usually 0.1 to 10% by weight, and preferably 0.5 to 5.0% by weight.

[0241] In one example, the content of the internal electron donor in the solid catalyst component for olefin polymerization is usually 1 to 50% by weight, preferably 5 to 40% by weight.

[0242] In one example, the content of the alkoxy group in the solid catalyst component for olefin polymerization is usually 10% by weight or less, and preferably 5% by weight or less.

[0243] <Olefin polymerization catalyst>

[0244] In one embodiment, the olefin polymerization catalyst can be produced by contacting the olefin polymerization solid catalyst component of the present invention with an organoaluminum compound using a known method, for example. In another embodiment, the olefin polymerization catalyst can be produced by contacting the olefin polymerization solid catalyst component of the present invention, an organoaluminum compound, and an external electron donor.

[0245] Therefore, in one embodiment, the olefin polymerization catalyst of the present invention comprises the solid catalyst component for olefin polymerization of the present invention and an organoaluminum compound. In another embodiment, the olefin polymerization catalyst of the present invention comprises the solid catalyst component for olefin polymerization of the present invention, an organoaluminum compound and an external electron donor.

[0246] The organoaluminum compound used in the present invention is a compound having one or more carbon-aluminum bonds, and specifically, the compounds described in Japanese Patent Application Laid-Open No. 10-212319 can be exemplified. Among them, trialkylaluminum, a mixture of trialkylaluminum and dialkylaluminum halide, or alkylaluminoxane is preferred, and triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, diethylaluminum chloride, a mixture of triethylaluminum and diethylaluminum chloride, or tetraethyldialuminoxane is more preferred.

[0247] As the external electron donor used in the present invention, compounds described in Japanese Patent No. 2950168, Japanese Patent Publication No. 2006-96936, Japanese Patent Publication No. 2009-173870 and Japanese Patent Publication No. 2010-168545 can be exemplified. Among them, oxygen-containing compounds or nitrogen-containing compounds are preferred. As oxygen-containing compounds, alkoxy silicon, ethers, esters and ketones can be exemplified. Among them, alkoxy silicon or ether is preferred.

[0248] The alkoxysilicon as the external electron donor is preferably a compound represented by any one of the following formulae (iv) to (vii).

[0249] R 2 h Si(OR 3 ) 4-h …(iv)

[0250] Si(OR4 )3(NR 5 R 6 )……(v)

[0251] Si(OR 4 )3(NR 7 )……(vi)

[0252] Si(OR 4 )2(NR 7 )2……(vii)

[0253] [Where R 2 is a hydrocarbon group having 1 to 20 carbon atoms or a hydrogen atom; R 3 is a hydrocarbon group having 1 to 20 carbon atoms; h is an integer satisfying 0≤h<4. 2 and R 3 If there are multiple R 2 and multiple R 3 They may be the same as or different from each other. 4 is a hydrocarbon group having 1 to 6 carbon atoms; R 5 and R 6 is a hydrogen atom or a hydrocarbon group having 1 to 12 carbon atoms; NR 7 It is a cyclic amino group having 5 to 20 carbon atoms.]

[0254] As R in the above formula (iv) 2 and R 3 The hydrocarbon group may be an alkyl group, an aralkyl group, an aryl group, an alkenyl group, etc. 2 and R 3 The alkyl group may be a straight-chain alkyl group such as methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl and n-octyl; a branched-chain alkyl group such as isopropyl, isobutyl, tert-butyl, isopentyl, neopentyl and 2-ethylhexyl; a cyclic alkyl group such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl and cyclooctyl, preferably a straight-chain alkyl group, branched-chain alkyl group or cyclic alkyl group having 1 to 20 carbon atoms. 2 and R 3 The aralkyl group as R includes benzyl and phenethyl, and is preferably an aralkyl group having 7 to 20 carbon atoms. 2 and R 3 The aryl group as R includes phenyl, tolyl and xylyl, and is preferably an aryl group having 6 to 20 carbon atoms. 2 and R 3 The alkenyl group may be a straight-chain alkenyl group such as vinyl, allyl, 3-butenyl and 5-hexenyl; a branched-chain alkenyl group such as isobutenyl and 5-methyl-3-pentenyl; a cyclic alkenyl group such as 2-cyclohexenyl and 3-cyclohexenyl, and preferably an alkenyl group having 2 to 10 carbon atoms.

[0255] Specific examples of the alkoxysilane represented by the above formula (iv) include: cyclohexylmethyldimethoxysilane, cyclohexylethyldimethoxysilane, diisopropyldimethoxysilane, tert-butylethyldimethoxysilane, tert-butyl-n-propyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, dicyclobutyldimethoxysilane, dicyclopentyldimethoxysilane, dicyclohexyldimethoxysilane, tetraethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, isobutyltriethoxysilane, vinyltriethoxysilane, sec-butyltriethoxysilane, cyclohexyltriethoxysilane, and cyclopentyltriethoxysilane.

[0256] As R in the above formulae (v), (vi) and (vii) 4 The hydrocarbon group of R includes alkyl, alkenyl, etc. 4 The alkyl group may be a straight-chain alkyl group such as methyl, ethyl, n-propyl, n-butyl, n-pentyl and n-hexyl; a branched-chain alkyl group such as isopropyl, isobutyl, tert-butyl, isopentyl and neopentyl; a cyclic alkyl group such as cyclopropyl, cyclobutyl, cyclopentyl and cyclohexyl, preferably a straight-chain alkyl group having 1 to 6 carbon atoms, and particularly preferably a methyl group and an ethyl group. 4 Examples of the alkenyl group include straight-chain alkenyl groups such as vinyl, allyl, 3-butenyl and 5-hexenyl; branched-chain alkenyl groups such as isobutenyl and 5-methyl-3-pentenyl; and cyclic alkenyl groups such as 2-cyclohexenyl and 3-cyclohexenyl, preferably straight-chain alkenyl groups having 2 to 6 carbon atoms.

[0257] As R in the above formula (v) 5 and R 6 The hydrocarbon group of R includes alkyl, alkenyl, etc. 5 and R 6 The alkyl group may be a straight-chain alkyl group such as methyl, ethyl, n-propyl, n-butyl, n-pentyl and n-hexyl; a branched-chain alkyl group such as isopropyl, isobutyl, tert-butyl, isopentyl and neopentyl; a cyclic alkyl group such as cyclopropyl, cyclobutyl, cyclopentyl and cyclohexyl, preferably a straight-chain alkyl group having 1 to 6 carbon atoms, and particularly preferably a methyl group and an ethyl group. 5 and R 6 Examples of the alkenyl group include straight-chain alkenyl groups such as vinyl, allyl, 3-butenyl and 5-hexenyl; branched-chain alkenyl groups such as isobutenyl and 5-methyl-3-pentenyl; and cyclic alkenyl groups such as 2-cyclohexenyl and 3-cyclohexenyl, preferably straight-chain alkenyl groups having 2 to 6 carbon atoms.

[0258] Specific examples of the alkoxysilane represented by the above formula (v) include: dimethylaminotrimethoxysilane, diethylaminotrimethoxysilane, di-n-propylaminotrimethoxysilane, dimethylaminotriethoxysilane, diethylaminotriethoxysilane, di-n-propylaminotriethoxysilane, methylethylaminotriethoxysilane, methyl-n-propylaminotriethoxysilane, tert-butylaminotriethoxysilane, diisopropylaminotriethoxysilane, and methylisopropylaminotriethoxysilane.

[0259] As NR in the above formulae (vi) and (vii) 7 Examples of the cyclic amino group include a perhydroquinolyl group, a perhydroisoquinolyl group, a 1,2,3,4-tetrahydroquinolyl group, a 1,2,3,4-tetrahydroisoquinolyl group and an octamethyleneimino group.

[0260] Specific examples of the alkoxysilane represented by the above formulae (vi) and (vii) include perhydroquinolyltriethoxysilane, perhydroisoquinolyltriethoxysilane, 1,2,3,4-tetrahydroquinolyltriethoxysilane, 1,2,3,4-tetrahydroisoquinolyltriethoxysilane, and octamethyleneiminotriethoxysilane.

[0261] The ether as the external electron donor is preferably a cyclic ether compound. The cyclic ether compound refers to a heterocyclic compound having at least one -COC- bond in the ring structure, more preferably a cyclic ether compound having at least one -COCOC- bond in the ring structure, and particularly preferably 1,3-dioxolane or 1,3-dioxane.

[0262] The external electron donor may be used alone or in combination of two or more.

[0263] As long as the olefin polymerization catalyst is generated, there is no particular limitation on the method of contacting the solid catalyst component for olefin polymerization, the organoaluminum compound and the external electron donor. The contact is carried out in the presence of a solvent or in the absence of a solvent. The contact mixture may be supplied to a polymerization tank, or each component may be supplied to a polymerization tank separately and contacted in the polymerization tank, or a contact mixture of any two components and the remaining components may be supplied to a polymerization tank separately and contacted in the polymerization tank.

[0264] The amount of the organoaluminum compound used is usually 0.01 to 1000 micromol, preferably 0.1 to 500 micromol, based on 1 mg of the solid catalyst component for olefin polymerization.

[0265] The amount of the external electron donor used is usually 0.0001 to 1000 micromol, preferably 0.001 to 500 micromol, and more preferably 0.01 to 150 micromol, based on 1 mg of the solid catalyst component for olefin polymerization.

[0266] <Olefin polymers>

[0267] The olefin polymer of the present invention is an olefin polymer having an envelope degree E2 calculated by the following formula (3) in the range of 0.820 to 0.885.

[0268] E2=LE2 / LS2 (3)

[0269] (In formula (3),

[0270] LE2 represents the envelope length of the olefin polymer obtained from an image of the olefin polymer photographed with a scanning electron microscope.

[0271] LS2 represents the actual circumference of the olefin polymer obtained from an image of the olefin polymer taken using a scanning electron microscope.)

[0272] The bulk density reduction (ΔBD) of the olefin polymer of the present invention due to heating calculated by the following formula (4) is preferably in the range of -0.012 to -0.000.

[0273] ΔBD = (bulk density at 60°C) - (bulk density at room temperature) (4)

[0274] <Method for producing olefin polymer>

[0275] The method for producing an olefin polymer of the present invention comprises the step of polymerizing olefin in the presence of the olefin polymerization catalyst of the present invention.

[0276] As olefins, ethylene and α-olefins having 3 or more carbon atoms can be exemplified. As α-olefins, linear monoolefins such as propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene and 1-decene can be exemplified; branched monoolefins such as 3-methyl-1-butene, 3-methyl-1-pentene and 4-methyl-1-pentene; cyclic monoolefins such as vinylcyclohexane; and combinations of two or more thereof. Among them, homopolymerization of ethylene or propylene or copolymerization of multiple olefins with ethylene or propylene as the main component is preferred. The combination of the above-mentioned multiple olefins may include a combination of two or more olefins, and may also include a combination of a compound having a polyunsaturated bond such as a conjugated diene, a non-conjugated diene and an olefin. It is particularly preferred that the olefin contains at least one component selected from propylene, ethylene and 1-butene.

[0277] The olefin polymer produced by the method for producing olefin polymers of the present invention is preferably an ethylene homopolymer, a propylene homopolymer, a 1-butene homopolymer, a 1-pentene homopolymer, a 1-hexene homopolymer, an ethylene-propylene copolymer, an ethylene-1-butene copolymer, an ethylene-1-hexene copolymer, a propylene-1-butene copolymer, a propylene-1-hexene copolymer, an ethylene-propylene-1-butene copolymer, an ethylene-propylene-1-hexene copolymer, or a polymer obtained by multi-step polymerization thereof.

[0278] In one embodiment, the method for forming the olefin polymerization catalyst of the present invention is preferably a method comprising the following steps:

[0279] (i) a step of polymerizing a small amount of olefin (the same as or different from the olefin used in the original polymerization (generally referred to as main polymerization)) in the presence of a solid catalyst component for olefin polymerization and an organoaluminum compound (in order to adjust the molecular weight of the generated olefin polymer, a chain transfer agent such as hydrogen or an external electron donor may be used) to generate a catalyst component whose surface is covered with the polymer of the olefin (this polymerization is generally referred to as prepolymerization, and thus the catalyst component is generally referred to as a prepolymerized catalyst component);

[0280] (ii) A step of contacting the prepolymerized catalyst component with an organoaluminum compound and an external electron donor.

[0281] The prepolymerization is preferably a slurry polymerization using an inert hydrocarbon such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, cyclohexane, benzene and toluene as a solvent.

[0282] The amount of the organoaluminum compound used in the step (i) is usually 0.5 to 700 mol, preferably 0.8 to 500 mol, particularly preferably 1 to 200 mol, per 1 mol of titanium atom in the solid catalyst component used in the step (i).

[0283] The amount of the olefin to be prepolymerized is usually 0.01 g to 1000 g, preferably 0.05 g to 500 g, particularly preferably 0.1 g to 200 g, per 1 g of the solid catalyst component for olefin polymerization used in the step (i).

[0284] The slurry concentration of the solid catalyst component for olefin polymerization in the slurry polymerization in the step (i) is preferably 1 to 500 g of the solid catalyst component for olefin polymerization per liter of solvent, and particularly preferably 3 to 300 g of the solid catalyst component for olefin polymerization per liter of solvent.

[0285] The prepolymerization temperature is preferably -20°C to 100°C, particularly preferably 0°C to 80°C. The partial pressure of the olefin in the gas phase during the prepolymerization is preferably 0.01 MPa to 2 MPa, particularly preferably 0.1 MPa to 1 MPa, but is not limited thereto for olefins that are liquid at the prepolymerization pressure and temperature. The prepolymerization time is preferably 2 minutes to 72 hours.

[0286] In the prepolymerization, as a method of supplying a solid catalyst component, an organoaluminum compound, and an olefin to a polymerization tank, there are exemplified: (1) a method of supplying a solid catalyst component and an organoaluminum compound, and then supplying an olefin; and (2) a method of supplying a solid catalyst component and an olefin, and then supplying an organoaluminum compound. As a method of supplying an olefin to a polymerization tank, there are exemplified: (1) a method of supplying an olefin sequentially in such a manner that the pressure in the polymerization tank is maintained at a predetermined pressure; and (2) a method of supplying a predetermined amount of an olefin in its entirety at once. In order to adjust the molecular weight of the olefin polymer obtained by the prepolymerization, a chain transfer agent such as hydrogen may be used.

[0287] In the prepolymerization, part or all of the electron-donating compound (C) used in the main polymerization may be used as needed. The amount of the electron-donating compound used in the prepolymerization is usually 0.01 mol to 400 mol, preferably 0.02 mol to 200 mol, and particularly preferably 0.03 mol to 100 mol, relative to 1 mol of titanium atoms contained in the solid catalyst component; the amount of the electron-donating compound used in the prepolymerization is usually 0.003 mol to 5 mol, preferably 0.005 mol to 3 mol, and particularly preferably 0.01 mol to 2 mol, relative to 1 mol of the organoaluminum compound.

[0288] In the prepolymerization, the method of supplying the electron donating compound to the polymerization tank is not particularly limited. Examples of the method include: (1) a method of supplying only the electron donating compound; and (2) a method of supplying a contact product of the electron donating compound and an organic aluminum compound. The olefin used in the prepolymerization may be the same as or different from the olefin used in the main polymerization.

[0289] As the method for the main polymerization, there can be exemplified: (1) a method for polymerizing olefins in the presence of a catalyst obtained by contacting a solid catalyst component, an organic aluminum compound and an electron donating compound; (2) a method for polymerizing olefins in the presence of a prepolymerization catalyst; and (3) a method for polymerizing olefins in the presence of a contact product of the prepolymerization catalyst, an organic aluminum compound and an electron donating compound.

[0290] The amount of the organoaluminum compound used in the main polymerization is usually 1 mol to 1000 mol, preferably 5 mol to 600 mol, per 1 mol of titanium atoms in the solid catalyst component.

[0291] The amount of the electron-donating compound used in the main polymerization is generally 0.1 mol to 2000 mol, preferably 0.3 mol to 1000 mol, and particularly preferably 0.5 mol to 800 mol, relative to 1 mol of titanium atoms contained in the solid catalyst component; the amount of the electron-donating compound used in the main polymerization is generally 0.001 mol to 5 mol, preferably 0.005 mol to 3 mol, and particularly preferably 0.01 mol to 1 mol, relative to 1 mol of the organoaluminum compound.

[0292] The polymerization temperature in the main polymerization is usually -30°C to 300°C, preferably 20°C to 180°C, and more preferably 50°C to 95°C. The polymerization pressure is not particularly limited, but is usually about normal pressure to about 100 kg / cm 2 , preferably about 2 kg / cm 2 ~About 50kg / cm 2 The polymerization method may be a batch method or a continuous method. Examples of the polymerization method include: a slurry polymerization method using an inert hydrocarbon solvent such as propane, butane, isobutane, pentane, hexane, heptane, and octane; a solution polymerization method using the solvent; a bulk polymerization method using an olefin that is liquid at the polymerization temperature as a medium; and a gas phase polymerization method. In particular, from the viewpoint of obtaining good powder properties, the main polymerization is preferably a gas phase polymerization method.

[0293] In addition, in the main polymerization, from the viewpoint of improving the powder properties, improving the polymer properties, and controlling the polymerization activity, it is preferred to add a polymerization activity inhibitor to the polymerization system during the main polymerization.

[0294] The polymerization activity inhibitor used herein refers to a compound that has the effect of reducing the polymerization activity of the catalyst in the main polymerization. For example, it can be listed as: electron-donating compounds such as alkoxysilanes, esters, and ethers; active hydrogen compounds such as alcohols and water; and oxygen-containing compounds that are gases at normal temperature and pressure such as oxygen, carbon monoxide, and carbon dioxide. It is preferred to use one or more of them. Among them, tetraethoxysilane, tetramethoxysilane, methanol, ethanol, propanol, butanol, oxygen or carbon monoxide are preferably used, and tetraethoxysilane, ethanol or oxygen is particularly preferred.

[0295] The polymerization activity inhibitor is used by adding it to the polymerization system during the main polymerization, and is believed to show the above-mentioned improvement effect by contacting with the polymer particles present in the polymerization system. The method of addition may be intermittent or continuous. The timing of addition may be when the main polymerization starts or before the prepolymerization is about to end. The polymerization activity inhibitor may be used as it is or after diluting it with an inert hydrocarbon solvent or the like.

[0296] In the main polymerization, a chain transfer agent such as hydrogen may be used to adjust the molecular weight of the olefin polymer to be obtained.

[0297] [Example]

[0298] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0299] <Envelope Degree of Olefin Polymerization Solid Catalyst Component (or Olefin Polymer)>

[0300] The solid catalyst component for olefin polymerization (or olefin polymer) was placed on a smooth plane using a conductive double-sided tape, and then carbon deposition was performed using a carbon deposition apparatus (manufactured by Vacuum Equipment Co., Ltd., VE-2030). Then, a plane image was obtained from a direction perpendicular to the plane on which the solid catalyst component for olefin polymerization (or olefin polymer) was placed using a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, FE-SEM).

[0301] For the solid catalyst component for olefin polymerization, the conditions of the scanning electron microscope were set to an acceleration voltage of 8 kV and an observation magnification of 1300 to 7000 times so that the envelope circumference of the solid catalyst component for olefin polymerization in the plane image was 1470 to 3020 pixels. Under these conditions, the pixel size was 0.014 μm / pixel to 0.076 μm / pixel.

[0302] For olefin polymers, the conditions of the scanning electron microscope were set to an acceleration voltage of 8 kV and an observation magnification of 40 to 110 times so that the envelope circumference of the olefin polymer in the plane image was 1655 to 5586 pixels. Under these conditions, the pixel size was 0.45 to 2.48 μm / pixel.

[0303] Next, based on the image of the solid catalyst component for olefin polymerization (or olefin polymer), the envelope perimeter and the actual perimeter are measured using an image analysis device NS2K-Pro 8.23 ​​(manufactured by Nano Systems Co., Ltd.), and the envelope degree E1 of the solid catalyst component for olefin polymerization and the envelope degree E2 of the olefin polymer are calculated using the above formula (1) and formula (3) (envelope degree = envelope perimeter / actual perimeter). It should be noted that the solid catalyst component for olefin polymerization photographed using a scanning electron microscope is actually an aggregate of small solid catalyst components for olefin polymerization.

[0304] For example, in Figure 5In the solid catalyst component for olefin polymerization (or olefin polymer) shown in , the "envelope perimeter" as indicated by the dotted line means the perimeter when the convex parts thereof are connected at the shortest distance. The "actual perimeter" as indicated by the solid line means the length of the contour thereof.

[0305] In this example, the envelope perimeter and actual perimeter of 30 particles of solid catalyst components for olefin polymerization (or olefin polymers) were measured, the envelope degree was calculated, and their average value was obtained. 30 particles of solid catalyst components for olefin polymerization with a particle size of 10 μm to 70 μm were selected. 30 particles of olefin polymers with a particle size of 100 μm to 3000 μm were selected.

[0306] <How to calculate the perimeter of the envelope>

[0307] (1) Figure 6 As shown in (a), find the point A0 where the camera's scan line first hits the object.

[0308] (2) Figure 6 As shown in (b), the straight line extending from point A0 in the horizontal direction is rotated to find point A1 where the straight line hits the object.

[0309] (3) Figure 6 As shown in (c), the straight line extending from point A1 in the horizontal direction is rotated in the same manner to find point A2 where the straight line hits the object.

[0310] (4) This operation is repeated until the straight line reaches point A0, and the length of each straight line is summed up as the envelope circumference.

[0311] Envelope circumference = length A0A1 + length A1A2 + length A2A3 ... + length A n A0

[0312] <Determination of Ti Atom Content in Solid Catalyst Component for Olefin Polymerization (Unit: % by Weight)>

[0313] The measurement was carried out by the hydrogen peroxide method described in the 4th edition of Experimental Chemistry Lecture (edited by the Chemical Society of Japan), volume 15, page 233. The solid catalyst component for olefin polymerization was decomposed by dilute sulfuric acid, and then an excess of hydrogen peroxide was added to prepare a sample. The characteristic absorption of the prepared sample at a wavelength of 410 nm was measured using a double beam spectrophotometer U-2001 (manufactured by Hitachi, Ltd.). Then, the Ti atom content in the solid catalyst component for olefin polymerization was determined based on the calibration curve.

[0314] <Determination of the content of phthalate component in the solid catalyst component for olefin polymerization (unit: weight %)>

[0315] The solid catalyst component for olefin polymerization was dissolved in N,N-dimethylacetamide to prepare a sample. The prepared sample was measured by gas chromatography internal standard method (according to JIS K0114:2012) using GC-2014 (manufactured by Shimadzu Corporation). Based on the obtained measured value, the phthalate component content in the solid catalyst component for olefin polymerization was calculated.

[0316] <Specific surface area of ​​solid catalyst component for olefin polymerization (unit: m 2 / g)>

[0317] The specific surface area of ​​the solid catalyst component for olefin polymerization was determined by the BET method based on the amount of nitrogen adsorption and desorption using BELSORP-mini2 manufactured by Microchip Bayer.

[0318] <Intrinsic viscosity [η]T of olefin polymer (unit: dl / g)>

[0319] A tetralin solution of an olefin polymer (three concentrations: 0.1 g / dl, 0.2 g / dl, and 0.5 g / dl) was prepared, and the reduced viscosity of the tetralin solution was measured at 135° C. using an Ubbelohde viscometer. The intrinsic viscosity of the olefin polymer was then determined by the calculation method described in “Polymer Solutions, Polymer Experiments 11” (published by Kyoritsu Publishing Co., Ltd. in 1982), page 491, i.e., by the extrapolation method of plotting reduced viscosity against concentration and extrapolating the concentration to zero.

[0320] <Content of copolymer component in olefin polymer (unit: weight %)>

[0321] The heat of fusion (unit: J / g) of olefin polymers above 151°C was measured using a differential scanning calorimeter (DSC). A sample (5 mg) of the olefin polymer was placed in an aluminum pan, set in a differential scanning calorimeter DSC8500 device (manufactured by PerkinElmer), heated to 230°C, kept at 230°C for 5 minutes, cooled to 0°C at 5°C / min, kept at 0°C for 5 minutes, and then heated to 200°C at 5°C / min to measure the melting curve. Regarding the temperature, the melting point of indium was set to 156.6°C for correction. The heat of fusion was calculated from the melting peak area above 151°C in the melting curve, and then the content of the copolymer component was calculated using the following formula (5).

[0322] Content of copolymer component = 100 - (heat of fusion above 151°C) × 0.91 (5)

[0323] <Contents of ethylene monomer units and 1-butene monomer units in olefin polymers (unit: weight %)>

[0324] An olefin polymer (200 mg) was dissolved in o-dichlorobenzene (3 mL) in a 10 mmφ test tube to prepare a sample. The 13C-NMR spectrum of the prepared sample was measured. The measurement conditions of the 13C-NMR spectrum were as follows.

[0325] ·Measurement temperature: 135℃;

[0326] Pulse repetition time: 10 seconds;

[0327] Pulse width: 45°;

[0328] Cumulative times: 2500 times;

[0329] Based on the obtained 13C-NMR spectrum, the contents of ethylene monomer units and 1-butene monomer units in the olefin polymer were determined according to the method described in the report of Cheng et al. (Macromolecules, 1991, No. 24, pp. 4813-4819).

[0330] <Decrease in bulk density of olefin polymer due to heating (unit: g / cm 3 )>

[0331] The bulk density of the olefin polymer was measured at room temperature (20 to 25° C.) and 60° C. according to ISO 60: 1977. Then, the decrease in bulk density due to heating (hereinafter also referred to as “ΔBD”) was calculated using the following formula (4).

[0332] ΔBD = (bulk density at 60°C) - (bulk density at room temperature) (4)

[0333] <Example 1: Solid catalyst component 1 for olefin polymerization>

[0334] (1) Synthesis of solid catalyst component precursor 1

[0335] The gas in a cylindrical reactor having an agitator and four baffles was replaced with nitrogen, and then hexane (803 L), diisobutyl phthalate (6.8 kg), tetraethoxysilane (350 kg) and tetrabutoxytitanium (39 kg) were added and stirred. While the temperature of the obtained mixture was maintained at 7° C., a dibutyl ether solution of butylmagnesium chloride (concentration: 2.2 mol / L, 760 kg) was added dropwise thereto over 5 hours. Q at this time was 0.25. The obtained mixture was stirred at 20° C. for 1 hour, and then toluene (503 L) was added and filtered. The obtained solid was washed with toluene (1102 L) 3 times, and then toluene (405 L) was added to obtain a slurry of a solid catalyst component precursor 1.

[0336] (2) Synthesis of Solid Catalyst Component 1 for Olefin Polymerization

[0337] The gas in a cylindrical reactor equipped with a stirrer and four baffles was replaced with nitrogen, and then the slurry of the solid catalyst component precursor 1 obtained in the above (1) was transferred using toluene (300 L). While stirring the obtained transferred product, a mixed solution of titanium tetrachloride (883 kg) and dibutyl ether (20 kg) was added thereto, followed by a toluene solution of phthaloyl chloride (concentration: 80% by volume, 80 kg). While maintaining the temperature of the obtained mixture at 110° C., the mixture was stirred for 5 hours and then filtered. While maintaining the temperature in the reactor at 110° C., washing with toluene (1103 L) was performed three times, and then toluene (488 L) was added to obtain a slurry.

[0338] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (376 kg), dibutyl ether (20 kg) and diisobutyl phthalate (17 kg) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then filtered. While the temperature in the reactor was maintained at 105° C., washing was performed twice with toluene (1103 L), and then toluene (515 L) was added to obtain a slurry.

[0339] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (375 kg) and dibutyl ether (20 kg) was added thereto. The obtained mixture was stirred for 1 hour while maintaining the temperature of the mixture at 105° C., and then filtered. While maintaining the temperature in the reactor at 110° C., washing with toluene (1103 L) was performed twice, and then toluene (536 L) was added to obtain a slurry.

[0340] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (375 kg) and dibutyl ether (20 kg) was added thereto. The obtained mixture was stirred for 1 hour while maintaining the temperature of the mixture at 105° C., and then filtered. While maintaining the temperature in the reactor at 105° C., a washing operation with toluene (1103 L) was performed 6 times, followed by a washing operation with hexane (1002 L) 4 times, and then dried to obtain a solid catalyst component 1 for olefin polymerization.

[0341] The obtained solid catalyst component 1 for olefin polymerization had LE1 of 122 μm (2239 pixels), LS1 of 141 μm (2581 pixels), E1 of 0.868, a Ti atom content of 1.6% by weight, and a phthalate component content of 10.5% by weight.

[0342] (3) Synthesis of olefin polymer 1

[0343] The interior of a stainless steel autoclave (hereinafter referred to as "autoclave 1") having an internal volume of 3 L and equipped with a stirrer was dried under reduced pressure, and then the gas in the autoclave 1 was replaced with argon gas and cooled. Then, the interior of the autoclave 1 was evacuated.

[0344] Heptane, triethylaluminum (2.6 mmol), cyclohexylethyldimethoxysilane (CHEDMS) (0.26 mmol) and the solid catalyst component 1 for olefin polymerization obtained in (2) above (33 mg) are brought into contact in a glass feeder. The obtained contact product is put into an autoclave 1. Then, liquefied propylene (50 g) and liquefied butane (400 g) are supplied to the autoclave 1, followed by hydrogen (partial pressure: 0.007 MPa). Then, the temperature in the autoclave 1 is raised to 60°C to start polymerization. 20 minutes after the start of polymerization, unreacted propylene and butane are discharged to the outside of the polymerization system, and the inside of the autoclave 1 is dried under reduced pressure. Then, triethylaluminum (2.6 mmol) is supplied to the autoclave 1 under pressure, followed by hydrogen (partial pressure: 0.004 MPa).

[0345] The autoclave 1 was connected to an autoclave with an internal volume of 3 L (hereinafter referred to as "autoclave 2"), and then the inside of the autoclave 2 was evacuated. Then, propylene (450 g), ethylene (20 g) and 1-butene (60 g) were supplied to the autoclave 2. Then, the temperature in the autoclave 2 was raised to 70°C, and the obtained mixed gas was continuously supplied to the autoclave 1, and polymerization was carried out for 150 minutes at a polymerization pressure of 0.8 MPa. Then, the gas in the autoclave 1 was purged to terminate the polymerization. The generated olefin polymer was dried under reduced pressure at 70°C for 1 hour, thereby obtaining an olefin polymer 1 (172 g).

[0346] The LE2 of the obtained olefin polymer 1 was 2358 μm (2175 pixels), the LS2 was 2728 μm (2519 pixels), the E2 was 0.864, and the intrinsic viscosity [η]T was 1.52 dl / g. The content of the copolymer component in the obtained olefin polymer 1 was 86% by weight. In addition, the content of the ethylene monomer unit in the copolymer component was 3.8% by weight, and the content of the 1-butene monomer unit was 6.3% by weight.

[0347] <Example 2: Solid catalyst component 2 for olefin polymerization>

[0348] (1) Synthesis of Solid Catalyst Component Precursor 2

[0349] The gas in a cylindrical reactor having an agitator and four baffles was replaced with nitrogen, and then hexane (1243 L), tetraethoxysilane (350 kg) and tetrabutoxytitanium (39 kg) were added and stirred. While the temperature of the obtained mixture was maintained at 17° C., a dibutyl ether solution of butylmagnesium chloride (concentration: 2.2 mol / L, 760 kg) was added dropwise thereto over 5 hours. The Q at this time was 0.37. The obtained mixture was stirred at 20° C. for 1 hour, and then toluene (306 L) was added and filtered. The obtained solid was washed with toluene (1104 L) 3 times, and then toluene (355 L) was added to obtain a slurry of a solid catalyst component precursor 2.

[0350] (2) Synthesis of Solid Catalyst Component 2 for Olefin Polymerization

[0351] The gas in a cylindrical reactor equipped with a stirrer and four baffles was replaced with nitrogen, and then the slurry of the solid catalyst component precursor 2 obtained in the above (1) was transferred using toluene (300 L). Toluene (54 L) was extracted from the obtained transferred product, and then a mixed solution of titanium tetrachloride (920 kg) and dibutyl ether (20 kg) was added thereto while stirring the obtained residue, followed by a toluene solution of phthaloyl chloride (concentration: 80% by volume, 70 kg). The obtained mixture was stirred for 5 hours while the temperature was maintained at 110° C., and then filtered. While the temperature in the reactor was maintained at 110° C., washing with toluene (1104 L) was performed three times, and then toluene (528 L) was added to obtain a slurry.

[0352] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (375 kg), dibutyl ether (20 kg) and diisobutyl phthalate (17 kg) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then filtered. While the temperature in the reactor was maintained at 110° C., washing was performed twice with toluene (1104 L), and then toluene (576 L) was added to obtain a slurry.

[0353] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (375 kg) and dibutyl ether (20 kg) was added thereto. The obtained mixture was stirred for 1 hour while maintaining the temperature of the mixture at 105° C., and then filtered. While maintaining the temperature in the reactor at 110° C., washing with toluene (1103 L) was performed twice, and then toluene (582 L) was added to obtain a slurry.

[0354] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (376 kg) and dibutyl ether (20 kg) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then filtered. While the temperature in the reactor was maintained at 105° C., washing was performed 3 times with toluene (1103 L), followed by washing 4 times with hexane (1003 L), and then dried to obtain a solid catalyst component 2 for olefin polymerization.

[0355] The obtained solid catalyst component 2 for olefin polymerization had LE1 of 69 μm (2201 pixels), LS1 of 75 μm (2412 pixels), E1 of 0.913, Ti atom content of 2.0 wt%, and phthalate component content of 9.4 wt%.

[0356] (3) Synthesis of olefin polymer 2

[0357] The interior of a stainless steel autoclave (hereinafter referred to as "autoclave 1") having an internal volume of 3 L and equipped with a stirrer was dried under reduced pressure, and then the gas in the autoclave 1 was replaced with argon gas and cooled. Then, the interior of the autoclave 1 was evacuated.

[0358] Heptane, triethylaluminum (2.6 mmol), cyclohexylethyldimethoxysilane (CHEDMS) (0.26 mmol) and the solid catalyst component 2 for olefin polymerization obtained in (2) above (30 mg) are brought into contact in a glass feeder. The obtained contact product is put into an autoclave 1. Then, liquefied propylene (50 g) and liquefied butane (400 g) are supplied to the autoclave 1, followed by hydrogen (partial pressure: 0.007 MPa). Then, the temperature in the autoclave 1 is raised to 60°C to start polymerization. 20 minutes after the start of polymerization, unreacted propylene and butane are discharged to the outside of the polymerization system, and the inside of the autoclave 1 is dried under reduced pressure. Then, triethylaluminum (2.6 mmol) is supplied to the autoclave 1 under pressure. Next, hydrogen (partial pressure: 0.004 MPa) is supplied.

[0359] The autoclave 1 was connected to an autoclave with an internal volume of 3 L (hereinafter referred to as "autoclave 2"), and then the inside of the autoclave 2 was evacuated. Then, propylene (450 g), ethylene (20 g) and 1-butene (60 g) were supplied to the autoclave 2. Then, the temperature in the autoclave 2 was raised to 70°C, and the obtained mixed gas was continuously supplied to the autoclave 1, and polymerization was carried out for 150 minutes at a polymerization pressure of 0.8 MPa. Then, the gas in the autoclave 1 was purged to terminate the polymerization. The generated olefin polymer was dried under reduced pressure at 70°C for 1 hour, thereby obtaining an olefin polymer 2 (166 g).

[0360] The LE2 of the obtained olefin polymer 2 was 1462 μm (2084 pixels), the LS2 was 1655 μm (2358 pixels), the E2 was 0.884, and the intrinsic viscosity [η]T was 1.61 dl / g. The content of the copolymer component in the obtained olefin polymer 2 was 85% by weight. In addition, the content of the ethylene monomer unit in the copolymer component was 4.0% by weight, and the content of the 1-butene monomer unit was 5.9% by weight.

[0361] <Example 3: Solid catalyst component 3 for olefin polymerization>

[0362] (1) Synthesis of Solid Catalyst Component Precursor 3

[0363] The gas in a cylindrical reactor having an agitator and four baffles was replaced with nitrogen, and then hexane (923 L), diisobutyl phthalate (7.8 kg), tetraethoxysilane (383 kg) and tetrabutoxytitanium (45 kg) were added and stirred. While the temperature of the obtained mixture was maintained at 5° C., a dibutyl ether solution of butylmagnesium chloride (concentration: 2.2 mol / L, 874 kg) was added dropwise thereto over 5 hours. Q at this time was 0.29. The obtained mixture was stirred at 35° C. for 2 hours, and then toluene (501 L) was added and filtered. The obtained solid was washed with toluene (1270 L) 3 times, and then toluene (451 L) was added to obtain a slurry of a solid catalyst component precursor 3.

[0364] (2) Synthesis of Solid Catalyst Component 3 for Olefin Polymerization

[0365] The gas in a cylindrical reactor equipped with a stirrer and four baffles was replaced with nitrogen, and then the slurry of the solid catalyst component precursor 3 obtained in the above (1) was transferred using toluene (302 L). While stirring the obtained transferred product, a mixed solution of titanium tetrachloride (1015 kg) and dibutyl ether (23 kg) was added thereto, followed by a toluene solution of phthaloyl chloride (concentration: 80% by volume, 94 kg). While the temperature of the obtained mixture was maintained at 110° C., it was stirred for 5 hours and then filtered. While the temperature in the reactor was maintained at 110° C., washing with toluene (1404 L) was performed three times, and then toluene (671 L) was added to obtain a slurry.

[0366] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (325 kg), dibutyl ether (23 kg) and diisobutyl phthalate (19 kg) was added thereto. The obtained mixture was stirred for 1 hour while maintaining the temperature at 105° C., and then filtered. While maintaining the temperature in the reactor at 110° C., a washing operation with toluene (1268 L) was performed once, and then toluene (674 L) was added to obtain a slurry.

[0367] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (325 kg) and dibutyl ether (23 kg) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then filtered. While the temperature in the reactor was maintained at 110° C., a washing operation with toluene (1268 L) was performed once, and then toluene (641 L) was added to obtain a slurry.

[0368] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (324 kg) and dibutyl ether (23 kg) was added thereto. The obtained mixture was stirred for 1 hour while maintaining the temperature of the mixture at 105° C., and then filtered. While maintaining the temperature in the reactor at 110° C., a washing operation with toluene (1268 L) was performed 6 times, followed by a washing operation with hexane (1153 L) 4 times, and then dried to obtain a solid catalyst component 3 for olefin polymerization.

[0369] The obtained solid catalyst component 3 for olefin polymerization had LE1 of 135 μm (2545 pixels), LS1 of 152 μm (2866 pixels), E1 of 0.889, a Ti atom content of 1.6% by weight, and a phthalate component content of 10.7% by weight.

[0370] (3) Synthesis of olefin polymer 3

[0371] The interior of a stainless steel autoclave (hereinafter referred to as "autoclave 1") having an internal volume of 5 L and equipped with a stirrer was dried under reduced pressure, and then the gas in the autoclave 1 was replaced with argon gas and cooled. Then, the interior of the autoclave 1 was evacuated.

[0372] Heptane, triethylaluminum (6.6 mmol), cyclohexylethyldimethoxysilane (CHEDMS) (0.66 mmol) and the solid catalyst component 3 for olefin polymerization obtained in (2) above (44 mg) are brought into contact in a glass feeder. The obtained contact product is put into an autoclave 1. Then, liquefied propylene (75 g) and liquefied butane (600 g) are supplied to the autoclave 1, followed by hydrogen (partial pressure: 0.007 MPa). Then, the temperature in the autoclave 1 is raised to 60°C to start polymerization. 20 minutes after the start of polymerization, unreacted propylene and butane are discharged to the outside of the polymerization system, and the inside of the autoclave 1 is dried under reduced pressure. Then, triethylaluminum (6.6 mmol) is supplied to the autoclave 1 under pressure, followed by hydrogen (partial pressure: 0.001 MPa).

[0373] The autoclave 1 was connected to an autoclave with an internal volume of 3 L (hereinafter referred to as "autoclave 2"), and then the inside of the autoclave 2 was evacuated. Then, propylene (450 g), ethylene (25 g) and 1-butene (60 g) were supplied to the autoclave 2. Then, the temperature in the autoclave 2 was raised to 70°C, and the obtained mixed gas was continuously supplied to the autoclave 1, and polymerization was carried out for 150 minutes at a polymerization pressure of 0.8 MPa. Then, the gas in the autoclave 1 was purged to terminate the polymerization. The generated olefin polymer was dried under reduced pressure at 70°C for 1 hour, thereby obtaining an olefin polymer 3 (379 g).

[0374] The LE2 of the obtained olefin polymer 3 was 2669 μm (2349 pixels), the LS2 was 3029 μm (2666 pixels), the E2 was 0.883, and the intrinsic viscosity [η]T was 1.61 dl / g. The content of the copolymer component in the obtained olefin polymer 3 was 92% by weight. In addition, the content of the ethylene monomer unit in the copolymer component was 4.0% by weight, and the content of the 1-butene monomer unit was 8.6% by weight.

[0375] <Example 4: Solid catalyst component 4 for olefin polymerization>

[0376] (1) Synthesis of Solid Catalyst Component Precursor 4

[0377] The gas in a cylindrical reactor with a stirrer and 4 baffles was replaced with nitrogen, and then hexane (177 mL), diisobutyl phthalate (1.6 g), tetraethoxysilane (79 mL) and tetrabutoxytitanium (9.1 g) were added and stirred. While maintaining the temperature of the obtained mixture at 7°C, a dibutyl ether solution of butylmagnesium chloride (concentration: 2.2 mol / L, 197 mL) was added dropwise thereto for 5 hours. The Q at this time was 0.19. The obtained mixture was stirred at 35°C for 2 hours and then filtered. The obtained solid was washed with toluene (238 mL) 3 times, and then toluene (83 mL) was added to obtain a slurry. The obtained slurry was stirred at 70°C for 1 hour to obtain a slurry of a solid catalyst component precursor 4.

[0378] (2) Synthesis of solid catalyst component for olefin polymerization

[0379] The gas in the reactor equipped with a stirrer and four baffles was replaced with nitrogen, and then the slurry (37 mL) of the solid catalyst component precursor 4 obtained in the above (1) was transferred. 10 mL of the supernatant toluene was extracted, and then a mixed solution of titanium tetrachloride (16 mL) and dibutyl ether (0.8 mL) was added thereto while stirring the obtained transfer, followed by a toluene solution of phthaloyl chloride (concentration: 80% by volume, 2.0 mL). While the temperature of the obtained mixture was maintained at 110° C., it was stirred for 5 hours, and then toluene (19 mL) was added and filtered. While the temperature in the reactor was maintained at 100° C., washing with toluene (38 mL) was performed three times, and then toluene (14 mL) was added to obtain a slurry.

[0380] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (5.1 mL), dibutyl ether (0.8 mL) and diisobutyl phthalate (0.5 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then toluene (28 mL) was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed three times with toluene (35 mL), and then toluene (14 mL) was added to obtain a slurry.

[0381] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (5.1 mL) and dibutyl ether (0.8 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then toluene (28 mL) was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed 3 times with toluene (35 mL), and then toluene (14 mL) was added to obtain a slurry.

[0382] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (5.1 mL) and dibutyl ether (0.8 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then 28 mL of toluene was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed 3 times with toluene (30 mL), followed by washing 4 times with hexane (31 mL), and then dried to obtain a solid catalyst component 4 for olefin polymerization.

[0383] The obtained solid catalyst component 4 for olefin polymerization had LE1 of 80 μm (2022 pixels), LS1 of 95 μm (2399 pixels), E1 of 0.845, Ti atom content of 2.4 wt%, and phthalate component content of 11.3 wt%.

[0384] (3) Synthesis of olefin polymer 4

[0385] The interior of a stainless steel autoclave (hereinafter referred to as "autoclave 1") having an internal volume of 5 L and equipped with a stirrer was dried under reduced pressure, and then the gas in the autoclave 1 was replaced with argon gas and cooled. Then, the interior of the autoclave 1 was evacuated.

[0386] Heptane, triethylaluminum (6.6 mmol), cyclohexylethyldimethoxysilane (CHEDMS) (0.66 mmol) and the solid catalyst component 4 for olefin polymerization obtained in the above (2) (43 mg) are brought into contact in a glass feeder. The obtained contact product is put into an autoclave 1. Then, liquefied propylene (75 g) and liquefied butane (600 g) are supplied to the autoclave 1, followed by hydrogen (partial pressure: 0.007 MPa). Then, the temperature in the autoclave 1 is raised to 60°C to start polymerization. 20 minutes after the start of polymerization, unreacted propylene and butane are discharged to the outside of the polymerization system, and the inside of the autoclave 1 is dried under reduced pressure. Then, triethylaluminum (6.6 mmol) is supplied to the autoclave 1 under pressure, followed by hydrogen (partial pressure: 0.001 MPa).

[0387] The autoclave 1 was connected to an autoclave with an internal volume of 3 L (hereinafter referred to as "autoclave 2"), and then the inside of the autoclave 2 was evacuated. Then, propylene (450 g), ethylene (25 g) and 1-butene (60 g) were supplied to the autoclave 2. Then, the temperature in the autoclave 2 was raised to 70°C, and the obtained mixed gas was continuously supplied to the autoclave 1, and polymerization was carried out for 70 minutes at a polymerization pressure of 0.8 MPa. Then, the gas in the autoclave 1 was purged to terminate the polymerization. The generated olefin polymer was dried under reduced pressure at 70°C for 1 hour, thereby obtaining an olefin polymer 4 (404 g).

[0388] The LE2 of the obtained olefin polymer 4 was 2454 μm (2145 pixels), the LS2 was 2898 μm (2536 pixels), the E2 was 0.848, and the intrinsic viscosity [η]T was 1.66 dl / g. The content of the copolymer component in the obtained olefin polymer 4 was 87% by weight. In addition, the content of the ethylene monomer unit in the copolymer component was 4.0% by weight, and the content of the 1-butene monomer unit was 7.7% by weight.

[0389] <Comparative Example 1: Solid catalyst component C1 for olefin polymerization>

[0390] (1) Synthesis of solid catalyst component precursor C1

[0391] The gas in a cylindrical reactor having an agitator and four baffles was replaced with nitrogen, and then hexane (923 L), tetraethoxysilane (383 kg) and tetrabutoxytitanium (44 kg) were added and stirred. While the temperature of the obtained mixture was maintained at 17° C., a dibutyl ether solution of butylmagnesium chloride (concentration: 2.2 mol / L, 874 kg) was added dropwise thereto over 5 hours. The Q at this time was 0.53. The obtained mixture was stirred at 35° C. for 1 hour, and then toluene (554 L) was added and filtered. The obtained solid was washed with toluene (1269 L) 3 times, and then toluene (407 L) was added to obtain a slurry of the solid catalyst component precursor C1.

[0392] (2) Synthesis of Solid Catalyst Component C1 for Olefin Polymerization

[0393] The gas in a cylindrical reactor equipped with a stirrer and four baffles was replaced with nitrogen, and then the slurry of the solid catalyst component precursor C1 obtained in the above (1) was transferred using toluene (303 L). While stirring the obtained transferred product, a mixed solution of titanium tetrachloride (1014 kg) and dibutyl ether (23 kg) was added thereto, followed by a toluene solution of phthaloyl chloride (concentration: 80% by volume, 90 kg). While maintaining the temperature of the obtained mixture at 110° C., the mixture was stirred for 5 hours and then filtered. While maintaining the temperature in the reactor at 110° C., washing with toluene (1404 L) was performed three times, and then toluene (592 L) was added to obtain a slurry.

[0394] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (324 kg), dibutyl ether (23 kg) and diisobutyl phthalate (38 kg) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then filtered. While the temperature in the reactor was maintained at 112° C., a washing operation with toluene (1270 L) was performed once, and then toluene (570 L) was added to obtain a slurry.

[0395] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (325 kg) and dibutyl ether (23 kg) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then filtered. While the temperature in the reactor was maintained at 112° C., a washing operation with toluene (1269 L) was performed once, and then toluene (580 L) was added to obtain a slurry.

[0396] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (325 kg) and dibutyl ether (23 kg) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then filtered. While the temperature in the reactor was maintained at 110° C., washing was performed three times with toluene (1270 L), followed by washing three times with hexane (1153 L), and then dried to obtain a solid catalyst component C1 for olefin polymerization.

[0397] The obtained solid catalyst component C1 for olefin polymerization had LE1 of 53 μm (2181 pixels), LS1 of 57 μm (2370 pixels), E1 of 0.921, a Ti atom content of 2.0 wt%, and a phthalate component content of 11.9 wt%.

[0398] (3) Synthesis of olefin polymer C1

[0399] The interior of a stainless steel autoclave (hereinafter referred to as "autoclave 1") having an internal volume of 5 L and equipped with a stirrer was dried under reduced pressure, and then the gas in the autoclave 1 was replaced with argon gas and cooled. Then, the interior of the autoclave 1 was evacuated.

[0400] Heptane, triethylaluminum (6.6 mmol), cyclohexylethyldimethoxysilane (CHEDMS) (0.66 mmol) and the solid catalyst component C1 (42 mg) for olefin polymerization obtained in the above (2) are contacted in a glass feeder. The obtained contact product is put into an autoclave 1. Then, liquefied propylene (75 g) and liquefied butane (600 g) are supplied to the autoclave 1, followed by hydrogen (partial pressure: 0.007 MPa). Then, the temperature in the autoclave 1 is raised to 60°C to start polymerization. 20 minutes after the start of polymerization, unreacted propylene and butane are discharged to the outside of the polymerization system, and the inside of the autoclave 1 is dried under reduced pressure. Then, triethylaluminum (6.6 mmol) is supplied to the autoclave 1 under pressure, followed by hydrogen (partial pressure: 0.001 MPa).

[0401] The autoclave 1 was connected to an autoclave with an internal volume of 3 L (hereinafter referred to as "autoclave 2"), and then the inside of the autoclave 2 was evacuated. Then, propylene (450 g), ethylene (25 g) and 1-butene (60 g) were supplied to the autoclave 2. Then, the temperature in the autoclave 2 was raised to 70°C, and the obtained mixed gas was continuously supplied to the autoclave 1, and polymerization was carried out for 90 minutes at a polymerization pressure of 0.8 MPa. Then, the gas in the autoclave 1 was purged to terminate the polymerization. The generated olefin polymer was dried under reduced pressure at 70°C for 1 hour, thereby obtaining an olefin polymer C1 (375 g).

[0402] The LE2 of the obtained olefin polymer C1 was 2038 μm (2957 pixels), the LS2 was 2309 μm (3350 pixels), the E2 was 0.886, and the intrinsic viscosity [η]T was 1.62 dl / g. The content of the copolymer component in the obtained olefin polymer C1 was 89% by weight. In addition, the content of the ethylene monomer unit in the copolymer component was 4.3% by weight, and the content of the 1-butene monomer unit was 7.6% by weight.

[0403] <Comparative Example 2: Solid catalyst component C2 for olefin polymerization>

[0404] (1) Synthesis of solid catalyst component precursor C2

[0405] The gas in a cylindrical reactor with a stirrer and 4 baffles was replaced with nitrogen, and then hexane (174 mL), diisobutyl phthalate (1.5 g), tetraethoxysilane (78 mL) and tetrabutoxytitanium (9.0 g) were added and stirred. While maintaining the temperature of the obtained mixture at 7°C, a dibutyl ether solution of butylmagnesium chloride (concentration: 2.2 mol / L, 194 mL) was added dropwise thereto for 5 hours. Q at this time was 0.11. The obtained mixture was stirred at 35°C for 2 hours and then filtered. The obtained solid was washed with toluene (238 mL) 3 times, and then toluene (83 mL) was added to obtain a slurry. The obtained slurry was stirred at 70°C for 1 hour to obtain a slurry of the solid catalyst component precursor C2.

[0406] (2) Synthesis of solid catalyst component for olefin polymerization

[0407] The gas in the reactor having an agitator and four baffles was replaced with nitrogen, and then the slurry (34 mL) of the solid catalyst component precursor C2 obtained in the above (1) was transferred. While stirring the obtained transferred product, a mixed solution of titanium tetrachloride (14 mL) and dibutyl ether (0.7 mL) was added thereto, followed by a toluene solution of phthaloyl chloride (concentration: 80% by volume, 1.7 mL). While maintaining the temperature of the obtained mixture at 110°C, the mixture was stirred for 5 hours, and then toluene (16 mL) was added and filtered. While maintaining the temperature in the reactor at 100°C, washing with toluene (34 mL) was performed three times, and then toluene (14 mL) was added to obtain a slurry.

[0408] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (4.5 mL), dibutyl ether (0.7 mL) and diisobutyl phthalate (0.4 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then toluene (25 mL) was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed three times with toluene (34 mL), and then toluene (14 mL) was added to obtain a slurry.

[0409] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (4.5 mL) and dibutyl ether (0.7 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then toluene (25 mL) was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed three times with toluene (30 mL), and then toluene (14 mL) was added to obtain a slurry.

[0410] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (4.5 mL) and dibutyl ether (0.7 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then 25 mL of toluene was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed 3 times with toluene (30 mL), followed by washing 4 times with hexane (28 mL), and then dried to obtain a solid catalyst component C2 for olefin polymerization.

[0411] The obtained solid catalyst component C2 for olefin polymerization had LE1 of 83 μm (2205 pixels), LS1 of 105 μm (2767 pixels), E1 of 0.800, Ti atom content of 1.9 wt%, and phthalate component content of 13.3 wt%.

[0412] (3) Synthesis of olefin polymer C2

[0413] The interior of a stainless steel autoclave (hereinafter referred to as "autoclave 1") having an internal volume of 5 L and equipped with a stirrer was dried under reduced pressure, and then the gas in the autoclave 1 was replaced with argon gas and cooled. Then, the interior of the autoclave 1 was evacuated.

[0414] Heptane, triethylaluminum (6.6 mmol), cyclohexylethyldimethoxysilane (CHEDMS) (0.66 mmol) and the solid catalyst component C2 (45 mg) for olefin polymerization obtained in the above (2) are contacted in a glass feeder. The obtained contact product is put into an autoclave 1. Then, liquefied propylene (75 g) and liquefied butane (600 g) are supplied to the autoclave 1, followed by hydrogen (partial pressure: 0.007 MPa). Then, the temperature in the autoclave 1 is raised to 60°C to start polymerization. 20 minutes after the start of polymerization, unreacted propylene and butane are discharged to the outside of the polymerization system, and the inside of the autoclave 1 is dried under reduced pressure. Then, triethylaluminum (6.6 mmol) is supplied to the autoclave 1 under pressure, followed by hydrogen (partial pressure: 0.001 MPa).

[0415] The autoclave 1 was connected to an autoclave with an internal volume of 3 L (hereinafter referred to as "autoclave 2"), and then the inside of the autoclave 2 was evacuated. Then, propylene (450 g), ethylene (25 g) and 1-butene (60 g) were supplied to the autoclave 2. Then, the temperature in the autoclave 2 was raised to 70°C, and the obtained mixed gas was continuously supplied to the autoclave 1, and polymerization was carried out for 65 minutes at a polymerization pressure of 0.8 MPa. Then, the gas in the autoclave 1 was purged to terminate the polymerization. The generated olefin polymer was dried under reduced pressure at 70°C for 1 hour, thereby obtaining an olefin polymer C2 (405 g).

[0416] The LE2 of the obtained olefin polymer C2 was 2768 μm (2561 pixels), the LS2 was 3395 μm (3139 pixels), the E2 was 0.818, and the intrinsic viscosity [η]T was 1.80 dl / g. The content of the copolymer component in the obtained olefin polymer C2 was 88% by weight. In addition, the content of the ethylene monomer unit in the copolymer component was 4.6% by weight, and the content of the 1-butene monomer unit was 7.5% by weight.

[0417] <Comparative Example 3: Solid catalyst component C3 for olefin polymerization>

[0418] (1) Synthesis of solid catalyst component precursor C3

[0419] The gas in a cylindrical reactor with a stirrer and 4 baffles was replaced with nitrogen, and then hexane (173 mL), diisobutyl phthalate (1.7 g), tetraethoxysilane (77 mL) and tetrabutoxytitanium (8.9 g) were added and stirred. While maintaining the temperature of the obtained mixture at 7°C, a dibutyl ether solution of butylmagnesium chloride (concentration: 2.2 mol / L, 192 mL) was added dropwise thereto for 5 hours. The Q at this time was 0.028. The obtained mixture was stirred at 35°C for 2 hours and then filtered. The obtained solid was washed with toluene (238 mL) 3 times, and then toluene (83 mL) was added to obtain a slurry. The obtained slurry was stirred at 70°C for 1 hour to obtain a slurry of the solid catalyst component precursor C3.

[0420] (2) Synthesis of Solid Catalyst Component C3 for Olefin Polymerization

[0421] The gas in the reactor having an agitator and four baffles was replaced with nitrogen, and then the slurry (34 mL) of the solid catalyst component precursor C3 obtained in the above (1) was transferred. While stirring the obtained transferred product, a mixed solution of titanium tetrachloride (14 mL) and dibutyl ether (0.7 mL) was added thereto, followed by a toluene solution of phthaloyl chloride (concentration: 80% by volume, 1.7 mL). While maintaining the temperature of the obtained mixture at 110° C., the mixture was stirred for 5 hours, and then toluene (16 mL) was added and filtered. While maintaining the temperature in the reactor at 100° C., washing with toluene (34 mL) was performed three times, and then toluene (12 mL) was added to obtain a slurry.

[0422] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (4.5 mL), dibutyl ether (0.7 mL) and diisobutyl phthalate (0.4 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then toluene (25 mL) was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed three times with toluene (34 mL), and then toluene (14 mL) was added to obtain a slurry.

[0423] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (4.5 mL) and dibutyl ether (0.7 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then toluene (25 mL) was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed 3 times with toluene (30 mL), and then toluene (13 mL) was added to obtain a slurry.

[0424] While stirring the obtained slurry, a mixed solution of titanium tetrachloride (4.5 mL) and dibutyl ether (0.7 mL) was added thereto. The obtained mixture was stirred for 1 hour while the temperature was maintained at 105° C., and then toluene (25 mL) was added and filtered. While the temperature in the reactor was maintained at 100° C., washing was performed 3 times with toluene (30 mL), followed by washing 4 times with hexane (28 mL), and then dried to obtain a solid catalyst component C3 for olefin polymerization.

[0425] The obtained solid catalyst component C3 for olefin polymerization had LE1 of 86 μm (2271 pixels), LS1 of 114 μm (2984 pixels), E1 of 0.765, Ti atom content of 2.0 wt%, and phthalate component content of 13.1 wt%.

[0426] (3) Synthesis of olefin polymer C3

[0427] The interior of a stainless steel autoclave (hereinafter referred to as "autoclave 1") having an internal volume of 5 L and equipped with a stirrer was dried under reduced pressure, and then the gas in the autoclave 1 was replaced with argon gas and cooled. Then, the interior of the autoclave 1 was evacuated.

[0428] Heptane, triethylaluminum (6.6 mmol), cyclohexylethyldimethoxysilane (CHEDMS) (0.66 mmol) and the solid catalyst component C3 (45 mg) for olefin polymerization obtained in the above (2) are contacted in a glass feeder. The obtained contact product is put into an autoclave 1. Then, liquefied propylene (75 g) and liquefied butane (600 g) are supplied to the autoclave 1, followed by hydrogen (partial pressure: 0.007 MPa). Then, the temperature in the autoclave 1 is raised to 60°C to start polymerization. 20 minutes after the start of polymerization, unreacted propylene and butane are discharged to the outside of the polymerization system, and the inside of the autoclave 1 is dried under reduced pressure. Then, triethylaluminum (6.6 mmol) is supplied to the autoclave 1 under pressure, followed by hydrogen (partial pressure: 0.001 MPa).

[0429] The autoclave 1 was connected to an autoclave with an internal volume of 3 L (hereinafter referred to as "autoclave 2"), and then the inside of the autoclave 2 was evacuated. Then, propylene (450 g), ethylene (25 g) and 1-butene (60 g) were supplied to the autoclave 2. Then, the temperature in the autoclave 2 was raised to 70°C, and the obtained mixed gas was continuously supplied to the autoclave 1, and polymerization was carried out for 100 minutes at a polymerization pressure of 0.8 MPa. Then, the gas in the autoclave 1 was purged to terminate the polymerization. The generated olefin polymer was dried under reduced pressure at 70°C for 1 hour, thereby obtaining an olefin polymer C3 (379 g).

[0430] The LE2 of the obtained olefin polymer C3 was 4212 μm (2504 pixels), the LS2 was 5393 μm (3194 pixels), the E2 was 0.786, and the intrinsic viscosity [η]T was 1.98 dl / g. The content of the copolymer component in the obtained olefin polymer C3 was 88% by weight. In addition, the content of the ethylene monomer unit in the copolymer component was 4.5% by weight, and the content of the 1-butene monomer unit was 7.5% by weight.

[0431]

[0432] Industrial Applicability

[0433] Compared with Comparative Examples 1 to 3, the bulk density reduction (ΔBD (g / cm 3)) is small. This means that the mutual adhesion between particles of the manufactured olefin polymer caused by the surface stickiness generated by heating is small. Therefore, if the olefin polymer is manufactured using the solid catalyst component for olefin polymerization of the present invention, the clogging of the polymerization device and the adhesion of the polymer on the wall of the polymerization device are improved. In addition, the productivity of the polymer is improved due to the reasons such as the weight of the olefin polymer that can be manufactured by the polymerization device becoming larger and the flow rate of the gas circulating in the polymerization device becoming larger.

Claims

1. An olefin polymer, wherein The envelope degree E2 of the olefin polymer calculated by the following formula (3) is in the range of 0.820 to 0.885, the particle size of the olefin polymer is 100 μm to 3000 μm, E2=LE2 / LS2 (3) In formula (3), LE2 represents the envelope perimeter of the olefin polymer obtained from an image of the olefin polymer taken with a scanning electron microscope, wherein the envelope perimeter refers to the perimeter when the convex parts of the olefin polymer are connected at the shortest distance. LS2 represents the actual circumference of the olefin polymer obtained from an image of the olefin polymer taken with a scanning electron microscope, The envelope degree E2 is calculated by the following method: using a conductive double-sided tape to place the olefin polymer on a plane, then using a carbon vapor deposition device to perform carbon vapor deposition, and then using a scanning electron microscope to obtain a plane image from a direction perpendicular to the plane where the olefin polymer is placed; then, based on the image of the olefin polymer, 30 particles of the olefin polymer with a particle size of 100μm to 3000μm are selected, and an image analysis device is used to measure the envelope circumference LE2 and actual circumference LS2 of the 30 particles of the olefin polymer, the envelope degree E2 is calculated, and their average value is calculated.

2. The olefin polymer according to claim 1, wherein The bulk density reduction (ΔBD) of the olefin polymer due to heating calculated by the following formula (4) is in the range of -0.012 to -0.000, ΔBD=(bulk density at 60°C)-(bulk density at room temperature) (4).

Citation Information

Patent Citations

  • Alpha-olefin polymerization catalyst and production of alpha-olefin polymer

    JP1998212319A

  • Solid catalyst component for producing propylene block copolymer, catalysts for producing propylene block copolymer and method for producing propylene block copolymer

    JP2004182981A

  • alpha-OLEFIN POLYMERIZATION CATALYST AND METHOD FOR PRODUCING alpha-OLEFIN POLYMER

    JP2006096936A

  • Solid catalyst component for olefin polymerization and production process thereof

    JP2009173870A

  • CATALYST FOR POLYMERIZATION OF alpha-OLEFIN AND MANUFACTURING METHOD FOR alpha-OLEFIN POLYMER

    JP2010168545A